GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 5559716 species occurrences available in GBIF matching the query: Country: Colombia. The dataset includes 5559716 records from 1779 constituent datasets: 3 records from Banco de datos florísticos del Herbario CHAP. 1 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 13 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 27 records from MfN - Fossil invertebrates III. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 59 records from Flora del Bosque de los Guayupes Acacias, Meta, Colombia. 26409 records from Herbario Pontificia Universidad Javeriana. 939 records from DMNH Birds. 1 records from arim. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 49 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 3 records from ENBI-Dataset of GART-GloBIS. 23 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 23 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 2 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 403 records from Vegetación de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 603 records from Recursos hidrobiológicos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia BIO. 8399 records from Paleobiology Database. 13 records from A taxonomic revision of the Neotropical myrmicine ant genus Lachnomyrmex Wheeler (Hymenoptera: Formicidae). 72 records from UF Florida Museum of Natural History Mammals. 1 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 42 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 8 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 4 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal). 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 4568 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 3497 records from Recopilación de Información de FLORA en la Jurisdicción de CORNARE, hasta el año 2015. 2 records from A synopsis of the Neotropical genus Protoneura (Odonata: Coenagrionidae). 13 records from UWIZM International Lepidoptera Collection. 3 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 12 records from Naturalis Biodiversity Center (NL) - Foraminifera. 89 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 2 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 2901 records from naturgucker. 4 records from Royal Ontario Museum - Entomology (ROME). 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 366 records from Anfibios y reptiles de la cuenca alta y media del río Bita, Vichada (Colombia). 64 records from Análisis ecológico de la ornitofauna de la ciénaga La Honda, Tanguí. 5 records from A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae. 1 records from NIAES Coleoptera Specimen Database. 10 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 3 records from Canadian Museum of Nature Crustacea Collection. 37 records from Entomology Collection at the Natural History Museum of Utah. 11 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 165 records from Anfibios y reptiles en el municipio Medina, Cundinamarca - Proyecto Colombia BIO. 1945 records from Registros biológicos de predios promocionados como Reservas Naturales de la Sociedad Civil-RNSC en el Cañón de Amaime, municipio El Cerrito, Valle del Cauca, Colombia.. 5 records from ALCB - Herbário Alexandre Leal Costa. 6 records from Australian National Insect Collection. 1968 records from MVZ Herp Collection (Arctos). 5 records from Colección de Referencia de Reptiles del Museo de Ciencias de la Universidad El Bosque. 285 records from Murciélagos observados en la transición Andino Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 270 records from Registros biológicos de aves Distrito de Manejo Integrado Musichi y Santuario de Fauna y Flora los Flamencos, La Guajira.. 62 records from Diptera Collection of Museum and Institute of Zoology PAS. 3421 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 5399 records from Harvard University Herbaria: All Records. 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 2 records from Revision and phylogeny of Hypotelus Erichson: a Neotropical genus of minute rove beetles (Coleoptera, Staphylinidae, Piestinae). 350 records from Estudio de la estructura genética espacial de la palma Elaeis oleifera. 2 records from TSB Lichen Herbarium. 1 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 14 records from Fiocruz/COLVEC - Coleção de Vetores da Doença de Chagas. 23410 records from AMNH Bird Collection. 3474 records from MVZ Bird Collection (Arctos). 250 records from Colección de Mamíferos – Universidad de la Amazonia. 243 records from Caracterización de coberturas vegetales en el páramo de Rabanal. 7527 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 1353 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 221 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 35 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 207 records from Naturalis Biodiversity Center (NL) - Crustacea. 16 records from The jumping lynx spider Oxyopes salticus Hentz, 1845 and its Neotropical relatives (Araneae: Oxyopidae). 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 3165 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Santuario de Flora y Fauna Los Colorados. 42 records from Global caridean shrimp fauna. 11 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 55 records from Fauna íctica del río Arquía, en las estribaciones del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 6 records from Ornithologie ZMK. 1 records from Palaeobiology collection, FAU Erlangen. 413272 records from DATAVES. 1375 records from Línea base biótica del proyecto de Restauración Ecológica Re-Viva La Primavera. 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 41 records from SDNHM Birds Collection. 1 records from Ibaraki Nature Museum, Mammals collection. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 6004 records from Colección Limnológica Universidad de Antioquia. 6 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 25 records from R - Herbário do Museu Nacional. 1 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 10 records from UCM Amphibian and Reptile Collection (Arctos). 12963 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 16 records from Inventario de Murciélagos Floreña I, Yopal, Casanare. 1102 records from Plantas laguna El Tinije. 2 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 27 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 6 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 20 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 76 records from CM Vertebrate Paleontology Collection. 251 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 14204 records from The System-wide Information Network for Genetic Resources (SINGER). 4 records from UCLA Donald R. Dickey Bird and Mammal Collection. 33 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 56 records from Lepidoptera specimen database of Japan. 98 records from Collection Vermes - ZMB. 36 records from Western Australian Museum provider for OZCAM. 6947 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 1 records from A review of the Pseudomyrmex ferrugineus and Pseudomyrmex goeldii species groups: acacia-ants and relatives (Hymenoptera: Formicidae). 706 records from Collection Mammalia SMF. 4 records from Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 20 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 38 records from Caracterizacion de Reptiles del Cerro de Chageradó, Frontino- Antioquia). 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 539 records from Insect Occurrence Data from MIZA. 27733 records from A global database for the distributions of crop wild relatives. 4685 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 4 records from Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae). 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 4 records from Bird Collection of Helsingborg Museums. 3 records from CNAV/Coleccion Nacional de Aves. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 11 records from Parasitic Platyhelminthes Collections. 8 records from Description of Notarius biffi n. sp. and redescription of N. insculptus (Jordan and Gilbert) (Siluriformes: Ariidae) from the eastern Pacific, with evidence of monophyly and limits of Notarius.. 1 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleovertebrates National Collection (MACNPv). 1 records from FUEL - Herbário da Universidade Estadual de Londrina. 697 records from Tejidos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 40 records from Herbarium Senckenbergianum (FR) - Fungi. 8513 records from Colección de Reptiles del Instituto Alexander von Humboldt. 56 records from UF Florida Museum Paleobotany. 21 records from Mastofauna presentes en la ciénaga de Guineo, Riosucio, Chocó. 2 records from DFO Maritimes Region Cetacean Sightings. 528 records from Mamíferos de Colombia. 14713 records from CM Birds Collection. 7 records from Notes on the genus Sakakibarella Creão-Duarte with description of three new species (Membracidae: Membracinae: Hoplophorionini). 374 records from Nannofossil abundance of Hole 15-151. 37 records from Avistamiento de Aves en la Reserva de la Sociedad Civil "El Diamante de las Aguas" Marzo 2017. 12 records from Algaterra Types. 321 records from Vegetación de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 79 records from Mamíferos medianos y grandes en la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 614 records from Fungi (S). 11 records from University of Ghana - Ghana Herbarium. 5 records from NCSM Mollusks Collection. 18805 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 769 records from Insectos de los Parques Ecológicos Distritales Humedales de Bogotá, D.C.. 15 records from Catálogo de los equinodermos recientes de México (Fase II). 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 1 records from Taxonomic Revision of the Ant-Acacias (Fabaceae, Mimosoideae, Acacia, Series Gummiferae) of the New World. 271 records from AMNH Invertebrate Paleontology Collection. 738 records from Plantas del municipio de Medina, Cundinamarca y San Juanito, Meta - Proyecto Colombia Bio. 286 records from Monitoreo biológico en la cuenca Sonso, campaña Agua ARA - RARE - CVC – Asociación Calidris. 1995 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 588 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 5796 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 3 records from DSMZ Collection of Filamentous Fungi and Yeasts. 60 records from NBM birds. 36342 records from Colección de artrópodos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 81 records from Distribución del gecko introducido Hemidactylus frenatus (Dumeril y Bribon 1836) (Squamata: Gekkonidae) en Colombia. 2 records from Gymnotus ardilai: a new species of Neotropical electric fish (Ostariophysi: Gymnotidae) from the Rio Magdalena Basin of Colombia.. 141 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 23 records from Revision of the Astyanax orthodus species-group (Teleostei: Characidae) with descriptions of three new species. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 233 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 1605 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 184 records from MSUM Ichthyology and Herpetology Collections. 9 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Review of Dissomphalus Ashmead (Hymenoptera, Bethylidae) from Panama, with key to the Central American species. 10 records from A new species and new records of the genus Oideterus Thomson, 1857 (Coleoptera: Cerambycidae: Prioninae: Anacolini) from Colombia. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 22 records from UCM Mammal Collection (Arctos). 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9212 records from Colección de Mamíferos del Instituto Alexander von Humboldt. 1933 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 823 records from Natural History Museum, Vienna - Herbarium W. 9 records from The genus Anisoscelis Latreille (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini): new species, taxonomical arrangements, distributional records and key. 18 records from Anfibios presentes en el Cerro Jánano. 26 records from Manchester Museum, University of Manchester, Botany Collection. 6 records from A new species of Metrobates Uhler, 1871 (Hemiptera: Heteroptera: Gerridae) from Colombia. 213 records from Poliquetos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMUV). 98 records from Canadian Museum of Nature Bird Collection. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 5 records from National Botanic Garden Belgium - Myxomycetes. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 2 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 3948 records from (Supplement 1) Relative abundance of planktic foraminifera in sediments of the last 560 kyr of ODP Hole 165-999A, Caribbean Sea. 1 records from Unraveling Ocyptamus and the Baccha legacy (Diptera: Syrphidae): redefinition of groups and new species descriptions. 93 records from Algas perifíticas del cerro Tacarcuna en el marco del proyecto Colombia BIO-2017. 4 records from Revision of the South American genus Tetragonopterus Cuvier, 1816 (Teleostei: Characidae) with description of four new species. 272 records from Museu Paraense Emilio Goeldi Herbarium. 157 records from Itami City Museum of Insects. 10 records from Mississippi Entomological Museum. 310 records from Botany (UPS). 1276 records from Escarabajos coprófagos (Scarabaeidae: Scarabaeinae) del eje cafetero Colombiano. 17 records from HAS - Herbário Alarich Rudolf Holger Schultz. 5 records from Lyman Entomological Museum (LEMQ). 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 1441 records from CAS Herpetology (HERP). 433 records from Mamíferos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 5 records from A revision of the genus Andesipolis (Hymenoptera: Braconidae: Mesostoinae) and redefinition of the subfamily Mesostoinae. 2 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 180 records from Bird specimens of the Yamashina Institute for Ornithology. 20 records from CNAC/Coleccion Nacional de Acaros. 602 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1461673 records from EOD - eBird Observation Dataset. 466 records from Nannofossil abundance of Hole 4-31. 7983 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 5974 records from SINGER Coordinator. 155 records from Avistamientos de Biodiversidad Marina / Marine Biodiversity Sightings. 1904 records from Escarabajos coprófagos de la cuenca alta y media del río Bita, Vichada (Colombia). 1863 records from University of Michigan Herbarium. 2 records from Species diversity of Rhinebothrium Linton, 1890 (Eucestoda: Rhinebothriidea) from Styracura (Myliobatiformes: Potamotrygonidae), including the description of a new species. 1 records from Conservación de la población de Loro Orejiamarillo (Ognorhynchus icterotis) en el piedemonte llanero, departamento del Meta. 11 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 36 records from Herpetology Collection. 641 records from sarce_rockyshores. 1 records from Actualización de la Colección de Microorganismos de importancia acuática. 40 records from URM - Herbário Pe. Camille Torrand. 26 records from ECatSym: Electronic World Catalog of Symphyta. 1 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 248 records from DUKE Bryophyte Collection. 1998 records from Aves de la cuenca media del río Bogotá. 1902 records from Fish Collection NRM. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 49 records from Equinodermos de las unidades ecológicas someras Expedición Seaflower Serranilla2017 - Proyecto Colombia BIO. 1 records from HST - Herbário Sérgio Tavares. 1 records from MVZ Bird Observations (Arctos). 10 records from Herbarium WRSL, Main Collection. 653 records from TNHC Herpetology Collection. 53 records from Lepidoptera - SNSD. 32 records from Fish Collection of Hokkaido University. 44 records from PACA-AGP - Herbarium Anchieta. 1412 records from Macaulay Library Audio and Video Collection. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. IV. Alopoglossidae, Gymnophthalmidae. 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 1 records from Colección de moldes endocraneanos del CENPAT. 1 records from Two new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from South America. 15523 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Ictiología. 20 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 16 records from The species of the Hypostomus cochliodon group (Siluriformes: Loricariidae).. 1 records from ECOT EcoTarium Ornithology Collection. 78 records from Helechos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 398 records from MVZ Mammal Collection (Arctos). 9125 records from Colección de anfibios del Museo de Historia Natural de la Pontificia Universidad Javeriana. 22 records from Mastofauna Presente en la Ciénaga de Montaño, Municipio del Carmen del Darién, Chocó. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 322 records from The Brown University Foraminiferal Data Base (BFD). 132 records from Collection Paleobotanique de l'Universite Paris 6. 1208 records from Herpetology. 47 records from Queensland Museum provider for OZCAM. 55 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 22 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 3 records from Collection Coleoptera SMF. 4765 records from Xeno-canto - Bird sounds from around the world. 2 records from Colección de Entomología - Curculionidae. 27 records from Caracterización de Reptiles del corredor biológico Cértegui - Yerrecuí - Amurrupá. Sector Amurrupá. 1267 records from International Barcode of Life project (iBOL). 100 records from Collection Herpetologie - SNSD. 1027 records from Inventario de Flora de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. Municipio de El Carmen de Viboral-Antioquia. 39 records from mel. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1614 records from Estonian University of Life Sciences. 882 records from Inventario de Fauna Vertebrada de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. 3 records from Shellfish specimens of the Nishinomiya Shell Museum, Japan. 1 records from Morphology and taxonomy of the orb-weaving spider genus Mecynogea, and a peculiar species of Argiope (Araneae, Araneidae). 3 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 7 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 3477 records from Aves laguna El Tinije. 10 records from ANTARCTIC PLANT DATABASE. 455 records from Collection Mollusca SMF. 813 records from Field Museum of Natural History (Botany) Fungi Collection. 239 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 14 records from ZUEC-PIS - Coleção de Peixes do Museu de Zoologia da UNICAMP. 3 records from Herbarium Senckenbergianum (GLM) - Lichenes. 162 records from Moscow University Herbarium (MW). 3 records from Revision of the Hybobathus arx and Pelecinobaccha summa species groups (Diptera: Syrphidae). 4 records from T. L. Hankinson Vertebrate Museum (EMU) Mammal Collection. 2208 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 10 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 195 records from Avifauna Asociadas al Cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 733 records from University of Michigan Museum of Zoology, Division of Mammals. 2 records from Birds Specimens. 18 records from Herpetos de un Área Degradada por Actividad Minera en la Costa Caucana. 4 records from Fundación Miguel Lillo - Colección Invertebrados. 7 records from Inventario de Murciélagos en la Finca la Reserva, El Perico, Yopal, Casanare. 32 records from Hymenoptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 581 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 290 records from Aves de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1 records from A new species of Umanella Gauld (Hymenoptera: Ichneumonidae: Pimplinae) from Colombia. 7 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 2012 records from Geneva Herbarium – General Collection (G). 1 records from Registro de Ateles belzebuth (mono araña) en el municipio de Yopal, departamento de Casanare. 1272 records from Avifauna de ocho localidades del corredor de conservación Paraguas – Munchique de Colombia.. 1011 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca). 1 records from SPSF - Herbário Dom Bento José Pickel. 69 records from Monitoreo de la flora presente en el páramo del Duende. 130 records from LSUMZ Herps Collection. 3093 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 2 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 243 records from Arizona State University Vascular Plant Herbarium. 11781 records from Colección de peces del Museo de Historia Natural de la Pontificia Universidad Javeriana. 117 records from IAC - Herbário do Instituto Agronômico de Campinas. 3 records from Global compendium of Aedes albopictus occurrence. 1 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 17058 records from Natural History Museum (London) Collection Specimens. 43 records from Inventarios de Murciélagos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 2 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 16041 records from Colección Ictiológica del Instituto Alexander von Humboldt. 1 records from UTEX Culture Collection of Algae at The University of Texas Living Algae Holdings. 445 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 7 records from Two new species of Quichuana Knab (Diptera: Syrphidae) from the paramo ecosystems in Colombia. 64 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1591 records from Herbario Orinocense Colombiano de la Universidad Nacional de Colombia sede Orinoquia (HORI). 550 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 11250 records from El Censo Neotropical de Aves Acuáticas en Colombia (CNAA): 2002 - 2011. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 45 records from Caracterización Ecológica de la avifauna del Cerro Jánano. 1331 records from CUMV Bird Collection. 10 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History. 11 records from Revision of the South American freshwater genus Plagioscion (Teleostei, Perciformes, Sciaenidae).. 3001 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 12489 records from AMNH Herpetology Collections. 9 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 438 records from Caracterización de la avifauna en una zona delimitada entre los municipios de Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño). 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 1 records from Nomenclatural and distributional notes on Neotropical Cerambycidae (Coleoptera). 41 records from CAS Invertebrate Zoology (IZ). 1 records from The Fungal Collection at the Botanische Staatssammlung München. 3 records from New genus and species of Neotropical Colobotheini (Coleoptera, Cerambycidae, Lamiinae). 3603 records from Phanerogamic Botanical Collections (S). 1 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 108 records from Rasgos funcionales de la vegetación en el cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 3 records from Herpetology. 2601 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 650 records from Fishbase. 944 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (siembra). 4 records from UEL - Coleção de Peixes - Museu de Zoologia da Universidade Estadual de Londrina. 189 records from Equinodermos de La Guajira Colombiana. 1 records from Sponges of the Guyana Shelf. 5739 records from Colección de mamíferos de la Universidad del Valle. 1 records from LSUMZ Mammal Tissues. 951 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 251 records from Colección Quirópteros Museo de La Salle Bogotá (MLS). 14 records from PlutoF platform observations. 4 records from Cliona acephala (Porifera: Demospongiae: Clionaida), a new encrusting excavating reef sponge from the Colombian Caribbean belonging to the Cliona viridis species complex. 1 records from CHAS Ornithology (Arctos). 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 212 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 3 records from Revisión del género Zabrotes para México (Coleoptera: Bruchidae). 17 records from Two new species and key to the salina group of the genus Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Colombia. 6795 records from Geographically tagged INSDC sequences. 14301 records from LACM Vertebrate Collection. 213 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 1 records from VANILLA RIVASII (ORCHIDACEAE), A NEW SPECIES FROM THE COLOMBIAN PACIFIC REGION. 76 records from South Australian Museum Australia provider for OZCAM. 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 13 records from A new species of Phrynus Lamarck, 1801 (Arachnida: Amblypygi), from Trinidad and Tobago, and Venezuela, with a redescription of Phrynus pulchripes (Pocock, 1894). 21 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 2 records from A checklist of the praying mantises of Peru: new records, one new genus (Piscomantis gen. n.) and biogeographic remarks (Insecta, Mantodea). 115 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 1871 records from Colección Teriológica de la Universidad Tecnológica del Chocó. 95 records from Elasmobranquios de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 64 records from Cleveland Museum of Natural History.. 29 records from Museu Paraense Emílio Goeldi - Ornithology Collection - Skin. 15759 records from Colección Zoológica de la Universidad del Tolima (CZUT) - Macroinvertebrados. 3 records from NCSM Ichthyology Collection. 14 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 19 records from Wilson Botanical Garden - Las Cruces Biological Station. 3 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 46 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 1316 records from Recurso hidrobiológico de los manglares de la Zona de Uso Sostenible de la Balsa (ZUSLB) y la Zona de Recuperación de Tinajones (ZRT). 50 records from Caracterización de la ornitofauna del Cerro Tacarcuna, Unguía, Chocó. 11 records from Reporte de Anfibios presentes en los corregimientos de Juanchaco y Ladrilleros (Buenaventura, Valle del Cauca) para el mes de septiembre de 2017. 34 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 1 records from MfN - Fossil invertebrates IIb. 1800 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Mastozoología. 9742 records from Alas del Arroz. 67 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 145 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 1663 records from Colección Ictiológica de la Universidad Industrial de Santander. 6 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 1 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 1 records from First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae). 15204 records from Aves de los Parques Ecológicos Distritales Humedales Bogotá, D.C.. 60 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 3 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 30 records from Fauna del Bosque de los Guayupes Acacias, Meta, Colombia. 23 records from New species and records of Cladiopsocus Roesler (Psocodea: ‘ Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia. 1744 records from Registros Primates Neotropicales Convocatoria APC. 2998 records from Colección de Peces Universidad Católica de Oriente. 215 records from Aves de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 17 records from CUMV Mammal Collection. 59862 records from Aarhus University Palm Transect Database. 2 records from HDJF - Herbário Dendrológico Jeanine Felfili. 1 records from Ghent University - Zoology Museum - Invertebrate collection. 2755 records from Collection Aves (bird skins) SMF. 21 records from Ictiologia Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 24 records from Nannofossil abundance of Hole 4-31. 5 records from Collection Crustacea - ZIM Hamburg. 8 records from MEXU/Leguminosae. 821 records from Coleção Entomológica do Museu Nacional / UFRJ. 18 records from Spider Mites Collection of Jean Gutierrez. 23 records from Caracterización de la ictiofauna de la ciénaga Honda, Tanguí. 316 records from Canadian Museum of Nature Herbarium. 73 records from Fiocruz/COLFLEB - Coleção de Flebotomíneos. 439 records from Implementación de la bioindicación en el Río Magdalena. 56 records from A taxonomic monograph of the assassin bug genus Zelus Fabricius (Hemiptera: Reduviidae): 71 species based on 10,000 specimens. 29 records from ZUEC-LEP - Coleção de Lepidoptera do Museu de Zoologia da UNICAMP. 14 records from UTEP Fossils (Arctos). 314 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 201 records from Tejidos de ejemplares colectados en el Páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 40 records from R. L. McGregor Herbarium Vascular Plants Collection. 211 records from Actividad de alerta del flamenco por turismo en el Parque Nacional Natural Santuario de Flora y Fauna Los Flamencos en Colombia. 420 records from Colección Zoológica de la Universidad del Tolima (CZUT) - Reptiles. 1 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 1 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 67 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 6 records from A revision and key for the tribe Diaphorolepidini (Serpentes: Dipsadidae) and checklist for the genus Synophis. 20 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 2 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 19 records from Polish gene bank – passport data of plants accessions which are important in human life. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1 records from Las monocotiledóneas mexicanas, una sinopsis florística. Parte II. 732 records from Colección Mastozoológica de la Universidad Industrial de Santander. 313 records from BMSM Bailey-Matthews National Shell Museum. 163 records from Entomofauna laguna El Tinije. 32 records from Caracterización Floristica del Paramo de Frontino o del Sol. 584 records from Registro de murciélagos del Cañón del Chicamocha, Santander (2013 - 2014). 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 37 records from Plathelminthes - SMF. 38 records from Peces de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 66 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 9 records from Vascular Plant Herbarium, Oslo (O). 1 records from UFMT - Herbário UFMT. 1 records from Cowan Tetrapod Collection - Mammals. 2 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 191 records from Estonian Museum of Natural History. 196 records from MLZ Bird Collection (Arctos). 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 1 records from A new species of Salamander (Caudata, Plethodontidae, Bolitoglossa) from Serranía de los Yariguíes, Colombia. 29 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 555 records from Plantas de los humedales de La Mojana, Colombia. 136 records from Proyecto peces Río Bita (Puerto Carreño- Vichada) de la Fundación Orinoquía. 464 records from Bocachico Prochilodus magdalenae (Characiformes: Prochilodontidae) en la cuenca media y baja del río Magdalena. 27 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 1 records from Mammals Specimens. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 1999 records from Composición florística y estructura de una parcela permanente en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 2020 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 1162 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 3 records from BCCM/MUCL Fungi. 3663 records from Texas A&M University Insect Collection. 5162 records from Biodiversidad de un bosque seco tropical del Valle Medio del río Magdalena: evaluación integrada a través de multitaxones. 11 records from Museo Nacional de Ciencias Naturales, Colección de Malacología: MNCN-Malac. 51 records from Tití Gris (Saguinus leucopus) en remanentes de bosque de los departamentos de Caldas y Antioquia. 5461 records from KUBI Herpetology Collection. 26 records from Caracterización de anfibios del corredor biológico Cértegui - Yerrecuí - Amurrupá. Sector Amurrupá. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 29 records from SMNS Herpetologie. 1 records from Taxonomic review of the genus Wasmannia.. 2068 records from Colección Zoológica de la Universidad del Tolima (CZUT)-Anfibios. 763 records from Caracterización de flora y fauna del Parque Nacional Natural Chingaza. 489 records from Bird Collection of Museum and Institute of Zoology PAS. 5 records from Sizing Ocean Giants. 1480 records from Relative abundance of Neogene nannofossils at ODP Site 165-999 from the Caribbean. 63 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 3 records from CNPE/Coleccion Nacional de Peces. 1 records from Collections data on ecology of bottom animal of the Southern ocean. 2 records from The mutillid wasps of the Dasymutilla paradoxa species-group (Hymenoptera, Mutillidae). 3133 records from Análisis de Integridad Biológica para el Distrito Regional de Manejo Integrado RUT Nativos.Convenio CVC- Univalle 108 de 2017. 29 records from MfN - Fossil vertebrates IV. 944 records from A geographic distribution database of Mononychellus mites (Acari: Tetranychidae) on cassava (Manihot esculenta). 5 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 24 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 1001 records from Colección Hidrobiológica del Chocó. 13 records from Herps Specimens. 11 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 3 records from The taxonomy of the American Ariadna Audouin (Araneae: Synspermiata: Segestriidae). 1628 records from LSUMZ Birds Collection. 575 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 2 records from ZFMK Hymenoptera collection. 8 records from Collection Aves (bird skeletons) SMF. 1 records from A new species of Hyloscirtus (Anura, Hylidae) from the Colombian and Venezuelan slopes of Sierra de Perijá, and the phylogenetic position of Hyloscirtus jahni (Rivero, 1961). 281 records from Inventarios de flora y fauna en bosques de niebla del municipio de Chámeza, Casanare. 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 84 records from Mamíferos, aves y peces de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 2 records from Mammalia fossil Kleinsäuger - SMF. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 29 records from Tortugas marinas de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 748 records from SIO Marine Vertebrate Collection. 3862 records from Fauna y flora del municipio de Lipa, Arauca. 14269 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 3 records from A new genus with seven species of the Subfamily Nopinae (Araneae, Caponiidae) from the Neotropical region. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 523 records from Anfibios de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 2 records from Review of the Neotropical spider wasp subgenus Anoplius (Dicranoplius) Haupt (Hymenoptera: Pompilidae), new comb.. 2 records from New records of Rhagoletis (Diptera: Tephritidae) in Colombia, with discussion on the morphological variations of some species. 1 records from Tricorythodes macuira (Ephemeroptera: Leptohyphidae), new species from Colombia. 322 records from Composición y distribución espacial del fitoplancton en aguas oceánicas del Caribe sur colombiano. 85 records from DORSA - German Orthoptera Collections. 11686 records from Escarabajos coprófagos (Coleoptera: Scarabaeidae: Scarabaeinae) de bosques secos Colombianos de la Colección Entomológica del Instituto Alexander von Humboldt. 11 records from Michigan State University Herbarium Lichens. 1711 records from Análisis de Integridad Biológica para el Parque Natural Regional Páramo del Duende. Convenio CVC- Univalle 108 de 2017. 66 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 5 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 2 records from Taxonomic revision of Neotropical Phyllocnistis Zeller, 1848 (Lepidoptera: Gracillariidae), with descriptions of seven new species and host plant associations. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 1 records from Carnet en Ligne. 2 records from Revisionary studies on the attine ant genus Trachymyrmex Forel. Part 3: The Jamaicensis group (Hymenoptera: Formicidae).. 4 records from New species, identification keys and notes on Lamiinae (Coleoptera, Cerambycidae) from the Neotropical region. 11 records from Inventario de Herpetología Floreña I, Yopal, Casanare. 1 records from Taxonomic revision of the flavopalliata species group of Signiphora (Hymenoptera: Signiphoridae). 1 records from African Rodentia. 227 records from Insect specimens of Himeji City Science Museum. 159 records from Inventario de invertebrados marinos del SFF Isla Malpelo, Proyecto Colombia BIO. 6677 records from Caracterización de aves asociadas a los cultivos de flores de la Sabana de Bogotá y el Oriente Antioqueño. 26 records from Caracterización Ecológica de la Ornitofauna del Humedal Costero Obregón. 355 records from Entomology Division, Yale Peabody Museum. 2 records from Museum of Southwestern Biology, Division of Arthropods. 3 records from SOUTHERN OCEAN ISOPODA. 4125 records from Colección de Entomología del Instituto de Ciencias Naturales (ICN-MHN-En). 15226 records from Colección Entomológica de Piedras Blancas. 11 records from TEPB - Herbário Graziela Barroso. 26 records from Caracterización de la avifauna presente en el río Tutunendo, Municipio de Quibdó-Chocó. 11181 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 1 records from Five new species of the genus Paromphacodes (Lepidoptera: Geometridae: Geometrinae) from High Andes in Ecuador. 84 records from UAZ Bird Collection. 8 records from South Caribbean Diversity. 3486 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejo de Páramos Frontino-Urrao y Citará. 125 records from MEXU/Plantas Vasculares. 199 records from NOAA Deep Sea Corals Research and Technology Program. 5 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 1316 records from University of Michigan Museum of Zoology, Division of Insects. 100 records from Arizona State University Lichen Collection. 26 records from Caracterización ecológica de la comunidad de herpetos de la ciénaga La Honda, Tanguí. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 2 records from A catalogue of the ants of Paraguay (Hymenoptera: Formicidae).. 110 records from University of Vienna, Institute for Botany - Herbarium WU. 5 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 152 records from Collection Ichthyologie - SNSD. 2 records from NYSM Birds. 17 records from Depuración de la colección y base de datos del Herbario CICY. Fase IV. 2 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 22 records from Análisis ecológico de la fauna en las fuentes abastecedoras de agua para comunidades indígenas de Osbezcac en la cuenca del rio Saija, Timbiquí - Cauca. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 3 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 431 records from Plantas Bosque Seco Chicamocha. 1 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 178 records from UWBM Invertebrate Paleontology Collection. 3154 records from Hormigas en cafetales con diferente intensidad de manejo en el departamento del Cauca. 17 records from Natusfera Citizen Science Observation Dataset. 258 records from Cnidarios del proyecto Macrofauna Corpoguajira. 6 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 17 records from Nannofossil assemblage in surface sediments. 182 records from NMNH Paleobiology Specimen Records. 26 records from Seven new species of the Neotropical electric fish Gymnotus (Teleostei, Gymnotiformes) with a redescription of G. carapo (Linnaeus).. 7 records from Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae). 38 records from Planktic foraminifera counts of sediment core V19-19. 4 records from Global subterranean fishes. 29 records from Caracterización Ecológica de la Mastofauna del Alto Galápagos. 353 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 1 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 142 records from UEC - Herbário da Universidade Estadual de Campinas. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 915 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 10 records from Allan Herbarium (CHR). 771 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 70 records from Planktic foraminifera abundance of Hole 15-153. 18 records from Herpetofauna del Alto Galápagos, San José del Palmar, Chocó. 593 records from Mamíferos voladores laguna El Tinije. 421 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 1 records from Coleção Entomológica Moure e Costa. 8 records from A new species of the catfish genus Cordylancistrus (Siluriformes, Loricariidae) from the Magdalena River, Tolima, Colombia. 3 records from Cercle des mycologues de Montréal Fungarium (CMMF). 15 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 54 records from Naturalis Biodiversity Center (NL) - Cnidaria. 6768 records from Composición florística y estructura de dos parcelas permanentes en bosques secos tropicales del municipio de Méndez, Tolima. 20 records from Comunidad de Reptiles presentes en el Cerro Jánano. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 3005 records from Colección Entomológica CDMB. 1 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 233 records from Colección Mastozoológica Universidad de los Llanos. 319 records from Colección nacional de palmas de Colombia - JBQ. 63 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 4533 records from Rasgos funcionales de plantas, anfibios y aves estudios bióticos complejos de páramos Chiles - Cumbal, La Cocha - Patascoy, Doña Juana - Chimayoy. 177494 records from Primer censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 2 records from Marie-Victorin Herbarium (MT) - Bryophytes. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 341 records from Evaluación bioecológica y ambiental de las áreas arrecifales del Caribe colombiano. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 60 records from Mamíferos de dos procesos para la conservación de relictos de bosque seco de la cuenca media – baja del Río Meléndez para la declaratoria de un Área Protegida Pública y para la Consolidación del SIMAP y fondo del agua de Cali. 165 records from Diversidad florística y estado de conservación en dos ventanas de paisaje de la UPR Tunjuelo priorizadas: Usme y Ciudad Bolivar, Bogotá. 2 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 3 records from HSU Wildlife Birds. 1 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 1 records from Taxonomic Review of Eumenes Latreille, 1802 (Hymenoptera, Vespidae, Eumeninae) from the New World. 34 records from Utah State University, Intermountain Herbarium. 163 records from Canadian Museum of Nature Palynology Collection. 104 records from Caracterización Florística de un Área Degradada por Actividad Minera en la Costa Caucana. 6745 records from Mammalogy Collection - Royal Ontario Museum. 2 records from Baillon Collection. 2071 records from Herbarium Berolinense. 27 records from CAS Entomology (ENT). 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 295 records from Computarización del Herbario ENCB, IPN. Fase IV. Base de datos de la familia Pinaceae y de distintas familias de la clase Magnoliopsida depositadas en el Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 117 records from Orchid Herbarium Collection. 2 records from SUI Vertebrate Collection. 8194 records from Colección de anfibios - Museo de Herpetología de la Universidad de Antioquia. 1 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 1 records from MEXU/Colección Histórica. 32 records from Crustáceos y Moluscos continentales del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 1 records from DBG Kathryn Kalmbach Herbarium. 2075 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 30 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 11 records from A new species of Brachychalcinus (Characiformes: Characidae) from the rio Xingu basin, Serra do Cachimbo, Brazil. 27 records from Arizona State University Hasbrouck Insect Collection. 14 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 168 records from Registros de quirópteros de tres localidades del caribe colombiano. 27 records from H.A. Stephens Herbarium. 1 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 843 records from Biodiversidad de Aves de las Reservas Naturales de la Sociedad Civil del Parque Natural Regional Páramo del Duende, Valle del Cauca, Colombia. 5 records from R-Criptogamos - Herbário do Museu Nacional - Criptogamos. 8 records from Mamíferos de un Área Degradada por Actividad Minera en la Costa Caucana. 22 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 5901 records from UF FLMNH Ichthyology. 2 records from Field Museum of Natural History (Geology) Fossil Invertebrates Collection. 6 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 2 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 29 records from Apteronotus caudimaculosus n. sp. (Gymnotiformes: Apteronotidae), a sexually dimorphic black ghost knifefish from the Pantanal, Western Brazil, with a note on the monophyly of the A. albifrons species complex.. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 2069 records from Field Museum of Natural History (Zoology) Fish Collection. 6 records from ZFMK Homoptera collection. 3 records from Museu Paraense Emílio Goeldi - Lacertilia Collection. 28 records from Collection Pantopoda SMF. 46 records from IZIKO South Africa Museum Collection (1800-2013). 161 records from Distribución del Manatí (Trichechus manatus) en la cuenca baja del río Sinú en el departamento de Córdoba. 2 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 2 records from Four new species of Callibaetis Eaton (Ephemeroptera: Baetidae), nymphal description of Callibaetis (Abaetetuba) fasciatus (Pictet) and keys for South American species of Callibaetis. 1362 records from Vulnerable marine ecosystems in the South Pacific Ocean region. 216 records from Registros biológicos del Humedal Santa María del Lago 1999-2013. 285 records from Colección de insectos de importancia médica del Instituto Nacional de Salud. 5 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 8 records from NBMB Herps. 1737 records from Aves Marinas y Playeras en el PNN Sanquianga y la Bocana de Iscuandé entre 2007 y 2009. 55 records from Caracterización de la Ornitofauna del Alto Galápagos, San José del Palmar, Chocó. 1 records from Canadian Museum of Nature Fossil Vertebrate Collection. 196 records from Inventario de Aves en la Finca Naranjitos; Aracal, Yopal, Casanare. 434 records from Aves de Caño Cristales, La Macarena, Meta. 1584 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 2 records from Herbario de la Universidad de Sevilla. 10 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 133 records from Mamíferos colectados en la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 568 records from Expedición Providencia I - INVEMAR. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 2 records from A revision of the Neotropical spider genus Nops MacLeay (Araneae: Caponiidae) with the first phylogenetic hypothesis for the Nopinae genera. 173 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 6 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 1512 records from University of Michigan Museum of Zoology, Division of Birds. 18554 records from Museum of Comparative Zoology, Harvard University. 1 records from DMNS Bird Collection (Arctos). 5 records from The rediscovery and redescription of Epigomphus pechumani Belle, 1970 (Odonata: Gomphidae), with a description of its female from the Western Colombian Andes. 144 records from Anfibios y Reptiles Bosque Seco Chicamocha. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 48 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 4 records from MPM Milwaukee Public Museum Herbarium. 1 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 69 records from Collection ornithologique A. Maës. 14 records from Gatesina colombiana n. gen. & n. sp. (Hymenoptera: Chalcidoidea, Eurytomidae), new Rileyinae associated with Myrcianthes (Myrtaceae) from Colombia. 1 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 98 records from University of Florida Vertebrate Paleontology. 1829 records from Naturalis Biodiversity Center (NL) - Aves. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 35 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 95 records from KUBI Ornithology Collection. 54 records from KUBI Ichthyology Collection. 1 records from The cnidarians collection (IK) of the Muséum national d'Histoire naturelle (MNHN - Paris). 17 records from CSIC-Real Jardín Botánico-Colección de Hepáticas (MA-Hepat). 438 records from Biodiversidad de Flora de las Reservas Naturales de la Sociedad Civil del Parque Natural Regional Páramo del Duende, Valle del Cauca, Colombia. 125 records from Aves del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 6 records from Collection Aves (spirit preserved) SMF. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 7 records from Herbarium of Taiwan Forestry Research Institute. 945 records from Inventario de Aves Mámbita. 110 records from Herbario de la Universidad de Sevilla, SEV-Historico. 16929 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves de los Complejos de Páramos de Sonsón y Urrao. 3000 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 2036 records from Caracterización biológica de la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 171 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad El Placer (Valle del Cauca). 118 records from Aves marinas de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 8 records from An updated list of the type specimens of Caelifera (Orthoptera) in the Museu Nacional, Rio de Janeiro. 12 records from Naturalis Biodiversity Center (NL) - Echinodermata. 16 records from HUCS - Herbário da Universidade de Caxias do Sul. 6 records from Three new species of Oxysarcodexia Townsend (Diptera: Sarcophagidae) from the Colombian Andes. 4 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 26 records from Colección de Referencia de Mamíferos del Museo de Ciencias de la Universidad El Bosque. 1600 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 2 records from University of New Mexico Herbarium. 2186 records from CAS Botany (BOT). 200 records from Colección de Quelonios Museo de La Salle Bogotá (MLS). 13 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 51 records from UB - Herbário da Universidade de Brasília. 52 records from Tallinn Botanic Garden. 4 records from Collection Ornithologie - ZSRO. 15 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 31 records from Publicación de la obra: American species of Acacia (Leguminosae; Mimosoideae). 2 records from NCSM Herpetology Collection. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 75 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramos "Guantiva -La Rusia", Colombia. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 54 records from Caracterización del caracol pala Lobatus gigas de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 30 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 19 records from Registro Herpetofauna de los Corregimientos de Juanchaco y Ladrilleros, Municipio de Buenaventura (Valle del Cauca) Septiembre de 2016. 58 records from Comunidad íctica de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 49 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 12109 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 1 records from Revision of the Neotropical water scavenger beetle genus Globulosis García, 2001 (Coleoptera: Hydrophilidae: Acidocerinae). 68 records from Invertebrate Paleontology Division, Yale Peabody Museum. 12 records from Paläontologie Marburg. 314 records from Peces laguna El Tinije. 32 records from Naturalis Biodiversity Center (NL) - Odonata. 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 655 records from Lista de árboles y arbustos del Bosque tropical seco del valle alto del río Magdalena, Colombia. 1 records from Invertebrate collection. 781 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 539 records from Aves de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 13 records from Generic synopsis of the jumping plant-lice (Hemiptera: Sternorrhyncha: Psylloidea) from Colombia. 217 records from Essig Museum of Entomology. 4 records from UWFC Ichthyology Collection. 118 records from Fiocruz/CTIOC - Coleção de Triatomíneos do Instituto Oswaldo Cruz. 1352 records from Implementación de la bioindicación en el Río Magdalena - 2016. 474 records from CABI Bioscience Fungus Collection. 58 records from Mamíferos laguna El Tinije. 403 records from Fauna de Caño Cristales, Sierra de La Macarena, Meta - Colombia. 79 records from Monitoreo de la avifauna presente en el páramo del Duende. 58 records from Lund Museum of Zoology (MZLU). 1 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 9 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 106 records from New species of Colombian Triplocania Roesler (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 141 records from Macrohongos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 690 records from Fishes of the flooded savannas of Paz de Ariporo, Meta River, Orinoco basin. 3 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 16 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 112 records from CUMV Fish Collection. 15 records from Botanical Research Intitute of Texas. 1675 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from MUST, Insecta. 32139 records from The New York Botanical Garden Herbarium (NY). 164 records from Naturalis Biodiversity Center (NL) - Paleobotany. 434 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Plantae. 139 records from Inventario de Aves en la Finca la Reserva, Yopal, Casanare. 471 records from Collection Arachnology SMF. 37 records from University of Tennessee Fungal Herbarium. 129 records from Herpetology Collection - Royal Ontario Museum. 72 records from University of Michigan Museum of Zoology, Division of Mollusks. 148 records from Museu Paraense Emilio Goeldi - Hymenoptera Collection. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 1 records from A revision of the Neotropical eumenine wasp genus Stenosigma Giordani Soika, 1978 (Hymenoptera, Vespidae). 2 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 2 records from HTSA - Herbário do Trópico Semiárido. 3 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 80 records from Type Specimen Database of Museum and Institute of Zoology PAS. 91 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 21 records from Brigham Young University Arthropod Museum. 2 records from Checklist of the micro- and anophthalmic soil-dwelling weevils of the world (Coleoptera: Curculionidae). 13 records from Coleópteros malacodermos (Phengodidae, Cantharidae, Lycidae, Lampyridae) del estado de Veracruz, México. 1668 records from Helechos de la jurisdicción de Corantioquia. 1071 records from herbario. 1 records from Royal BC Museum - Herbarium (V). 2 records from Ophiuroidea collections of the Zoological Institute Russian Academy of Sciences. 566 records from Registros de la Caracterización de vegetación y flora del POMCA de la SZH Cuenca del Río Tapias y Otros Directos al Cauca. 261 records from Seaflower ll: Cayo Serrana- Colecciones biológicas de la universidad CES - Proyecto Colombia BIO. 2382 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del piedemonte de Arauca, municipio de Tame. 69 records from Fundación Miguel Lillo - Colección Herpetológica. 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 439 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 3 records from Museu Paraense Emilio Goeldi - Araneae Collection. 1777 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 26 records from Anfibios y reptiles en el municipio de San Juanito, Meta - Proyecto Colombia BIO. 33 records from Los musgos de México. 62 records from Collection Malakologie - SNSD. 216 records from Recent Invertebrates Specimens. 14 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 208 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 1 records from UTEP Insects (Arctos). 258 records from Collection Pisces SMF. 2 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 36 records from MEXU/Tipos de plantas vasculares. 4 records from Collection of Heteroptera. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 4 records from UAZ Mammals. 8 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 98 records from Colección Nacional de Heliconias. 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 80 records from Field Museum of Natural History (Botany) Lichen Collection. 220 records from Inventario de Mamíferos Mámbita. 111 records from Caracterización ecológica de reptiles presentes en los bosques subxerofíticos de Unguía, Chocó. 1226 records from Aves del municipio de Cimitarra, Santander - Proyecto Santander BIO. 4254 records from Mosquito Occurrence Dataset. 11 records from Canadian Museum of Nature Mammal Collection. 6 records from Biodiversitätsdatenbank des Landes Salzburg. 215 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 24 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Foraminifera National Collection (MACNFo). 1 records from NCSM Mammals Collection. 3 records from VIC - Herbário da Universidade Federal de Viçosa. 16650 records from Colección general del plantas vasculares del Herbario JBB. 75540 records from Colección de Entomología del Instituto Alexander von Humboldt. 8 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 326 records from Peces de las unidades ecológicas someras Expedición Seaflower Serranilla 2017 - Proyecto Colombia BIO. 34037 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 82 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 124 records from Anfibios y reptiles de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 2864 records from RBINS DaRWIN. 1 records from A new species of Decaphora Franganillo, 1931 (Araneae, Sparassidae, Sparianthinae) from Colombia, with an identification key for all known species of the genus. 3006 records from Plantas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 11720 records from Colección Viva del Jardín Botánico de Bogotá. 281 records from Investigación prioritaria hacia el conocimiento y conservación de tortugas amenazadas del bosque seco tropical colombiano Mesoclemmys dahli (Carrachina) y Chelonoidis carbonaria (Morrocoy). 64 records from Caracterización Ecológica de la Fauna del Páramo de Tatamá. 45 records from Parcela Permanente en el Pantano Martos. 50 records from Microorganismos asociados con la filósfera de plantas de Espeletia en el PNN los Nevados. 6 records from A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini). 519 records from Aves MZS. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 17 records from Reporte de avistamientos de oso palmero (Myrmecophaga tridactyla Linnaeus, 1758) en el área de influencia de Llanos 58, Puerto López, Meta, Colombia. 1 records from Herbario Gaspar Xuarez (BAA) - Facultad de Agronomía - Universidad de Buenos Aires. 16 records from Global Butterfly Information System (GloBIS). 110405 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 266 records from Registros de flora de las caracterizaciones rápidas de coberturas en los municipios de Beltrán y Guataquí, Cundinamarca. 1 records from A new species of Cornutalis Sakakibara (Membracidae: Smiliinae: Acutalini) from Colombia. 341 records from Collection Herpetology SMF. 869 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 18 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 79 records from Comunidad de Peces un Área Degradada por Actividad Minera en la Costa Caucana. 1 records from The South American spider genera Mesabolivar and Carapoia (Araneae, Pholcidae): new species and a framework for redrawing generic limits. 2 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 3 records from Denver Museum of Nature & Science - Entomology. 269 records from The nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 15 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Revision of the amphiamerican genus Mysidium Dana, 1852 (Crustacea: Mysida: Mysidae), with descriptions of two new species and the establishment of two new subgenera. 839 records from UF Invertebrate Zoology. 1 records from Herbier de Strasbourg. 3551 records from Paleobiology Database. 2 records from MVZ Hildebrand Collection (Arctos). 3782 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Perijá. 1 records from Review of Dissomphalus Ashmead, 1893 (Hymenoptera, Bethylidae) from Espíri- to Santo, Brazil, with description of twenty-one new species. 8 records from Colección de Referencia de Urocordados del Museo de Ciencias de la Universidad El Bosque. 27 records from DSMZ Prokarya Collection Catalogue. 1503 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 1660 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 39 records from Equinodermos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 14321 records from Herbario de la Universidad Industrial de Santander. 14 records from California State University, Long Beach Mammals. 229 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther. 85 records from KUBI Mammalogy Collection. 162 records from University of Michigan Museum of Zoology, Division of Fishes. 2 records from Colección de Reptiles. 108516 records from ICN - Universidad Nacional de Colombia. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 108 records from Vert Paleo Specimen. 2 records from Palaeontological collections National Museum of Natural History Luxembourg. 3034 records from Caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 3 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 15 records from CNIN/Coleoptera. 4 records from MICROBIS database. 43 records from Senckenberg - CeDAMar Resource. 100 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 191 records from Herpetofauna laguna El Tinije. 7 records from CAS Geology (GEO). 3248 records from UTA Herpetology. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5697 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 6 records from Vascular Plant Herbarium, UiB. 332 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 13647 records from Field Museum of Natural History (Zoology) Bird Collection. 1898 records from Registros biológicos Parcela permanente HATOVIAL SAS en Barbosa, Antioquia. 1 records from Rutgers University, Chrysler Herbarium - Mycology Collection. 12 records from University of Florida Invertebrate Paleontology. 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 2024 records from Tejidos de insectos recolectados en trampas Malaise en los departamentos de Santander, Antioquia y Vichada - Proyecto Colombia Bio. 2 records from University of Tennessee Lichen Herbarium. 898 records from Tejidos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 4 records from Opiliones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 106 records from Evaluación de la presencia de 'Marmosa robinsoni' e inventario de mamíferos en el Departamento del Atlántico. 5 records from Mammal collection, Natural History Museum, University of Oslo. 12 records from Computarización del Herbario ENCB. Fase II. Base de datos de los ejemplares de la familia Burseraceae y Nyctaginaceae y base de datos digitalizada de los ejemplares tipo de plantas vasculares del Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 41 records from Sukkulentensammlung Zürich. 226 records from Tejidos colectados en la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 4457 records from Herbario Universidad del Quindío. 2014 records from Tejidos de Plantas, Anfibios y Aves, en estudios bióticos de los Complejos de Páramos Chiles - Cumbal, La Cocha-Patascoy y Doña Juana - Chimayoy. 8 records from CAS Mammalogy (MAM). 1815 records from Inventarios de flora y fauna en el piedemonte de los municipios Aguazul, Tauramena y Yopal del departamento de Casanare. 121 records from Herbarium of Namur. 1 records from UAM Bird Collection (Arctos). 41 records from Seguimiento y monitoreo del oso andino en la jurisdicción de Corpoguavio. 2 records from Collection Bryozoa SMF. 1001 records from Coleópteros de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 99392 records from Monitoreo Ambiental del Proyecto La Colosa. 639 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidroeléctrica Cucuana. 2017-B. 1060 records from Biodiversidad de grupos funcionales de microorganismos en el Parque Nacional Natural de Los Nevados, Colombia. 1 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 65 records from Inventario de aves del SFF Isla Malpelo, Proyecto Colombia BIO. 1 records from Guadeloupe_Insectes. 4126 records from Cruzando el Caribe - Construyendo la capacidad para el ecoturismo en el Darién y Urabá. 26624 records from LACM Entomology Collection. 10 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 111 records from Insecta collection of Museum of Natural and Environmental History, Shizuoka. 4937 records from Colección de Peces de la Universidad de Antioquia. 148 records from Tejidos colectados en la ventana de biodiversidad Filandia, Quindío, Colombia. 20 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Actuopalynology National Collection (BAPa). 6 records from HRCB - Herbário Rioclarense. 3 records from pins. 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa). 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 2948 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 2 records from Jardín Botánico de Córdoba: Herbarium COA. 9 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 276 records from Colección Mastozoológica de la Universidad Distrital Francisco José de Caldas. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 430 records from Colección de Referencia de Moluscos del Museo de Ciencias de la Universidad El Bosque. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 193 records from Establecimiento de línea base de fauna terrestre para el AID y AII de la Pequeña Central Hidroeléctrica Riofrío. 2017.. 9 records from William Nylander lichen collection. 95 records from Colección de Herbario. 127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba. 204 records from UWBM Mammalogy Collection (Arctos). 20 records from Taxonomic revision of Coniceromyia Borgmeier (Diptera: Phoridae), with the description of three new species from Brazil. 302 records from Mamíferos del piedemonte de la sabana de la Orinoquia. 1 records from Checklist and comments on the jumping plant-lice (Hemiptera: Psylloidea) from the Indian subcontinent. 10 records from University of British Columbia Herbarium (UBC) - Algae Collection. 176 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 72 records from Mamíferos en el Ecoparque Pance - Cali, Fase I Proceso de declaratoria de un área protegida de carácter público. 17 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 136 records from Escarabajos estercoleros (Coleoptera: Scarabaeinae) asociados a dos fincas ganaderas de Rionegro, Antioquia (Colombia). 201 records from Plantas de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 2459 records from WFVZ Bird Collections. 2 records from HPL - Herbário do Jardim Botânico Plantarum. 3 records from Two new Metacephalus DeLong & Martinson, 1973 species (Hemiptera: Cicadellidae: Portanini) from Brazil and proposed synonymy with Paraportanus Carvalho & Cavichioli, 2009. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 432 records from CSIC-Real Jardín Botánico-Colección de Musgos (MA-Musci). 18217 records from Coleccion de Ictiología del Instituto de Ciencias Naturales (ICN-MHN-Ic). 78 records from Bacterias y Actinobacterias aisladas del PNN los Nevados para estudios de actividad antimicriobana. 27 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 2195 records from Museo Laboratorio de Entomología (MENT-UT). 1 records from Revision of Diplosynapsis Enderlein, 1914 (Diptera, Asilidae, Asilinae) with description of four new species. 86 records from SPF - Herbário da Universidade de São Paulo. 3 records from Trichomycterus santanderensis: A new species of troglomorphic catfish (Siluriformes, Trichomycteridae) from Colombia.. 2 records from TTRS Ornithology. 2 records from Description of a new alpheid shrimp, Automate isabelae sp. nov. (Decapoda, Caridea, Alpheidae) found in fish stomach contents of the lane snapper Lutjanus synagris (Linnaeus, 1758), from the west coast of Florida, Gulf of Mexico. 20 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 3867 records from Reef Life Survey: Global reef fish dataset. 2 records from Propuesta para sistematizar la colección palinológica de polen reciente y fósil del IGLUNAM. 187 records from Arizona State University Amphibian and Reptile Collection. 1 records from ARC-PPRI: Chalcidoidea Collection (1900-2010). 14 records from Northern Territory Museum and Art Gallery provider for OZCAM. 190 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 655 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 2 records from BoGART. 7868 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 7822 records from Proyecto COL88611 para la conservación y uso sostenible de ecosistemas secos. 4 records from Las monocotiledóneas mexicanas, una sinopsis florística. 3 records from Computarización de la Colección Nacional de Peces del Instituto de Biología UNAM. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 10 records from A revision of the cis-andean species of the genus Brycon Müller & Troschel (Characiformes: Characidae). 130 records from Museu Paraense Emílio Goeldi - Diptera Collection. 4347 records from Aves Acuáticas en el Caribe Colombiano Entre 2007 y 2009. 7 records from R-Tipos - Herbário do Museu Nacional - Tipos. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 24 records from Checklist of Cerambycidae, Disteniidae and Vesperidae (Coleoptera) primary types of the Museu de Zoologia, Universidade de São Paulo, São Paulo, Brazil. 22 records from The Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 22 records from Herpetofauna del Alto del Buey, Bahía Solano, Chocó. 19 records from Herbarium Senckenbergianum (FR). 54 records from Invertebrate Zoology Division, Yale Peabody Museum. 1000 records from Colección Limnológica del Chocó. 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 1953 records from MBM - Herbário do Museu Botânico Municipal. 231 records from UCM Bird Collection (Arctos). 1 records from Estudio sistemático y ecológico del género Tigridia (Iridaceae). 25 records from Scale insects (Hemiptera: Coccomorpha) on sugarcane in Colombia, with description of a new species of Tillancoccus Ben-Dov (Coccidae). 699 records from Censo abundancia de aves en los Parques Nacionales Naturales de Bahía Malaga, Portete y Old Providence. 124 records from Colección de Entomología - Diptera - Ceratopogonidae. 1 records from West Virginia Wesleyan College Katharine B. Gregg Orchid Pollinator Collection. 116 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 4059 records from Registros biológicos a partir de actividades de pesca deportiva en los Llanos Orientales. 436 records from Naturalis Biodiversity Center (NL) - Porifera. 175 records from Natural History Museum, University of Tartu. 63 records from Actualización de la Colección de Artrópodos con importancia médica (CAIM), Laboratorio de Entomología, InDRE. 24 records from Comunidad de Herpetos Presentes en la Ciénaga de Montaño, Municipio del Carmen de Atrato. 447 records from Orthoptera del Museo de Entomología de la Universidad del Valle. 120 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 71 records from Christopher Walker collection of Glomeromycotan fungi. 503 records from Mamíferos: Colección Universidad de Caldas. 16 records from Catálogo de insectos de la colección del Centro de Entomología. 1 records from A revision of the Neotropical tortoise beetle genus Eurypedus Gistel 1834 (Coleoptera: Chrysomelidae). 9 records from CNHE/Coleccion Nacional de Helmintos. 15 records from Inventario de Corales del SFF Isla Malpelo, Proyecto Colombia BIO. 28 records from Mastofauna presente en el Alto del Buey, Bahía Solano, Chocó. 14 records from Vertebrate Paleontology Division, Yale Peabody Museum. 11 records from University of Tennessee at Chattanooga. 33 records from BCCM/LMG Bacteria collection. 2 records from Desert Botanical Garden Herbarium. 5 records from CNCR/Colección Nacional de Crustaceos. 185 records from Planktic foraminifera counts in surface sediment samples. 22 records from Ictiofauna Asociada a los Cativales del Municipio de Riosucio, como Aspecto Relevante dentro de la Estructura Ecológica Principal del Chocó Biogeográfico. 7 records from Jardin botanique de Montréal (JBM). 7 records from SANT Herbarium vascular plants collection. 523 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 15 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 5361 records from Colección Ornitológica de la Universidad del Valle. 101 records from Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN). 128 records from Global compendium of Aedes aegypti occurrence. 51 records from Colección de Aráceas del Jardín Botánico San Jorge. 52 records from Anfibios presentes en las lagunas del municipio del Medio Baudó. 4 records from Fish collection, Natural History Museum, University of Oslo. 14 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 17 records from Caracterización Ecológica de la Mastofauna del Cerro Tacarcuna, Unguía, Chocó. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 109 records from First visual occurrence data for deep-sea cnidarians in the South-western Colombian Caribbean. 38 records from GSPB Prokarya Catalogue. 3207 records from Establecimiento de línea base para el monitoreo de especies de plantas de interés para la conservación. 20 records from Colección de Referencia de Anfibios del Museo de Ciencias de la Universidad El Bosque. 6 records from Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species. 6 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 26014 records from Base de Datos de Flora de la Cuenca del Río Orinoco en Colombia. 2 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 13 records from Naturalis Biodiversity Center (NL) - Mammalia. 122 records from MBML-Aves - Coleção de Aves MBML. 20 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 997 records from Herbario HUAZ Enrique Forero. 1040 records from Anfibios y Reptiles reportados en humedales del departamento de Córdoba. 3 records from Ghent university - Zoology Museum - Nematod Collection. 1 records from Odonata from protected areas in Colombia with new records and description of Cora verapax sp. nov. (Zygoptera: Polythoridae). 48 records from Fauna herpetológica de los Parques Ecológicos Distritales Humedales Bogotá, D.C.. 18 records from New species, new records and notes in Cerambycidae from Colombia. 7 records from Mollusca collection of National Museum of Nature and Science. 11 records from NCSM Ornithology Collection. 15 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 103 records from MSB Mammal Collection (Arctos). 2 records from A new genus and two new species of congrid eels (Teleostei: Anguilliformes: Congridae) from the Indo-West Pacific, with a redescription and osteology of Chiloconger dentatus.. 2 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 2363 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 158101 records from NMNH Extant Specimen Records. 183 records from Museums Victoria provider for OZCAM. 141 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 172 records from Questagame weekly feed. 497 records from SysTax - Zoological Collections. 85 records from CMNH Birds Collection. 1 records from The genus Rosalba Thomson, 1864 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 79998 records from Herbario Universidad de Antioquia (HUA). 12 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 974 records from Registros de vertebrados durante el convenio 105- 2017 entre Panthera y la CVC. 732 records from A geographic distribution database of the cassava whitefly complex (Hemiptera, Aleyrodidae) and their associated parasitoids and hyperparasitoids (Hymenoptera). 77 records from Peces asociados a sistemas acuáticos del río Yarí, Amazonía Colombiana. 3 records from Anymals+plants - Citizen Science Data. 2 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 355 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 3 records from CRCM Vertebrate Collection. 20 records from A new species of the catfish genus Cordylancistrus (Siluriformes, Loricariidae) from the Sierra Nevada de Santa Marta, Colombia. 44 records from Registros de artrópodos la familia Baetidae, orden Ephemeroptera del Instituto de Biodiversidad Neotropical, Tucumán, Argentina.. 61 records from Registros restauración ecológica- Magdalena medio. 310 records from TTU Mammals Collection. 22 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 720 records from Insect specimens of Kashihara City Museum of Insect. 26 records from Aves marinas de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 23 records from Fossil (WSHN-FO). 224 records from Partial Amphibians Collection. 173 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4 records from Studies in Colombian Caelifera and adjacent territories: Ciglianacris, a new genus of Andean Melanoplinae (Orthoptera: Acrididae). 4 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 1211 records from MEXU/Colección de Briofitas. 13 records from CZE National PGR Inventory. 287 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Phyllobates terribilis (Valle del Cauca). 5 records from Alpheus luiszapatai, a new species of rare and colorful deep water alpheid shrimp (Crustacea: Decapoda: Alpheidae) from Arusí, Chocó Department, Pacific Coast of Colombia. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 30 records from The Vascular Plants Collection of the University of Goettingen. 10 records from Caracterizacion Ecologica de la Fauna de Anfibios Presentes en la Zona de Influencia de la Parte Alta del Rio Guangui. 5 records from DAV UC Davis Center for Plant Diversity. 4 records from Ouellet-Robert entomological collection (QMOR). 3990 records from Herpetofauna y avifauna de los municipios de Villeta y Guaduas (Cundinamarca), en el contexto de la vulnerabilidad del territorio al cambio climático. 27 records from Mamíferos Asociados al Cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 69 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1288 records from University of South Florida Herbarium (USF). 4 records from Revision of Thaumatocranaus Roewer, 1932, with description of two new species (Opiliones: Laniatores: Gonyleptoidea). 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 301 records from Colección de Mamíferos - Universidad del Quindío. 16 records from Mollusca Collection - Museu Nacional/UFRJ. 511 records from Plantas del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 1 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 12 records from Collection Ornithologie - SNSD. 8 records from Review of Gonatocerus (Hymenoptera: Mymaridae) in the Neotropical region, with description of eleven new species. 2447 records from Universidad Autónoma de Madrid, Biología, Acalypha. 4 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Types. 27 records from New species and records of earthworms (Annelida, Oligochaeta) in plantain cropping systems in Colombia's coffee-growing region. 245 records from Collection Thysanoptera SMF. 154 records from CONN. 18 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 69 records from The avian collection at the Natural History Museum, Oslo, Norway. 9021 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 40 records from Inventario de Herpetología en el Área Sujeta a Acuerdos de Conservación Voluntaria Quebrada Aguazula, Rincón del Soldado, Yopal. 1 records from MfN - Fossil plants (Mesophytic). 595 records from Aves de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 5578 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 99 records from CAS Ornithology (ORN). 530 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 20159 records from Herbario Universidad de Caldas - FAUC. 1 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 314 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramo "El Almorzadero", Colombia. 17 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 1 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 8 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 590 records from Aves Bosque Seco Chicamocha. 12 records from Revisiting the spider genus Eutichurus Simon, 1897 (Araneae, Eutichuridae): new species and complementary descriptions. 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 434 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 1392 records from Rasgos funcionales de plantas, anfibios y aves de estudios bióticos en el Complejo de Páramos Chingaza. 334 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 270 records from Plantas de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 3 records from Taxonomic revision of the crab spider genus Epicadus Simon, 1895 (Arachnida: Araneae: Thomisidae) with notes on related genera of Stephanopinae Simon, 1895. 3 records from New taxa and some clarification of the tribe Steirodontini (Orthoptera: Tettigoniidae; Phaneropterinae): Tenth contribution to the suprageneric organization of Neotropical phaneropterines. 31923 records from iNaturalist Research-grade Observations. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 1 records from A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 194 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 56 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 92 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 10 records from University of Arizona Insect Collection. 504 records from Dieta y preferencias alimenticias de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 41 records from Botany Division, Yale Peabody Museum. 125 records from Anfibios y Reptiles de Caño Cristales, La Macarena, Meta. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 34 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Naturalis Biodiversity Center (NL) - Coleoptera. 1 records from Hymenoptera collection of National Museum of Nature and Science. 7 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 13 records from Description of a new species of the genus Chaetostoma from the Orinoco River drainage with comments on Chaetostoma milesi Fowler, 1941 (Siluriformes: Loricariidae). 30 records from Bryophyte herbarium TRH, NTNU University Museum. 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 10 records from University of South Carolina, A. C. Moore Herbarium. 293 records from Macrofauna, entomofauna y vegetación vascular de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 210 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 91 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 37 records from Auckland Museum Botany Collection. 11 records from FBIP:IZIKO-UCT:Historical Survey (1930-1980). 990 records from Mamíferos de 14 municipios del Departamento del Valle del Cauca para el fortalecimiento de RNSC y Caracterización de Predios Adquiridos para la Conservación de Cuencas. 41 records from PRECIS. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 1 records from Taxonomic considerations on Lobocneme Rehn, 1911 and Paroxyopsis Rehn, 1911 and a new synonymy (Insecta Mantodea: Stagmatopterinae). 39 records from Macrohongos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 9 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 77 records from Plantas alimenticias incluidas en la dieta local en el municipio de Montería, Córdoba. 94 records from Collection Cnidaria SMF. 37 records from New Mexico State Collection of Arthropods. 25 records from Análisis de las poblaciones de oso palmero (Myrmecophaga tridactyla) en el Departamento del Meta. 4810 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV). 1979 records from University of California Museum of Paleontology. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 6663 records from Colección de anfibios y reptiles del Laboratorio de Herpetología de la Universidad del Valle (UV-C). 1152 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 232 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 117 records from Fiocruz/CCER - Coleção de Ceratopogonidae. 44 records from International Collection of Microorganisms from Plants (ICMP). 3 records from University of Tennessee Vascular Herbarium. 1356 records from Naturalis Biodiversity Center (NL) - Mollusca. 8 records from LSUMZ Mammals Collection. 745 records from Hongos formadores de micorrizas arbusculares de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 66 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 38 records from UWBM Ornithology Collection. 2338 records from CAS Ichthyology (ICH). 115 records from Mamíferos de los Parques Ecológicos Distritales de Humedales de Bogotá, D.C.. 132 records from Peces de agua dulce en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 112 records from Caracterización de Flora de la Reserva Forestal Protectora Regional Brisas del Rincón. 99 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 105 records from CNMA/Colección Nacional de mamíferos. 216 records from Monitoreo biológico en la cuenca Dagua - Subcuenca La Guinea ARA - RARE - CVC – Asociación Calidris. 5067 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 68 records from Fauna Asociada a los Cativales del Municipio de Riosucio, como Aspecto Relevante dentro de la Estructura Ecológica Principal del Chocó Biogeográfico. 8 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: MAMMALIA_FZ. 14404 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves del Complejo de Páramos Almorzadero y Tamá. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 2838 records from Vertebrados de los humedales de La Mojana, Colombia. 18006 records from Colección del Herbario PSO de la Universidad de Nariño. 23 records from Museu Paraense Emílio Goeldi - Ichthyology Collection. 5 records from The types of Phasmida in the Natural History Museum, London, UK. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 28 records from Invertebrates Collection of the Swedish Museum of Natural History. 5 records from Revision of world Ooderella Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae), with description of the first males for the genus. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 13 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 11 records from Desarrollar las actividades tendientes al manejo, conocimiento y conservación del Comino crespo (Aniba perutilis hemsl.), formuladas en el plan de conservación para la especie en el departamento del Meta. 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 259 records from AUM Fish Collection. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 285 records from The Lichen Collection at the Botanische Staatssammlung München. 1 records from Ghent University - Zoology Museum - Vertebrate collection. 1 records from Studies on neotropical Phasmatodea XVII: Revision of Phantasca Redtenbacher, 1906, with the descriptions of six new species (Phasmatodea: Diapheromeridae: Diapheromerinae). 4494 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. 763 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 2413 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2007. 5 records from The taxonomic and phylogenetic status of some poorly known Anolis species from the Andes of Colombia with the description of a nomen nudum taxon. 197 records from Monitoreo biológico en la cuenca Dagua - Subcuenca Bitaco, campaña ARA - RARE - CVC – Asociación Calidris. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 340 records from Arachnida Araneae do Museu Nacional (MNRJ ARAC ARAN). 10 records from On the Neotropical spider Subfamily Masteriinae (Araneae, Dipluridae). 337 records from Caracterización de coberturas vegetales en el páramo de Santurbán. 3027 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 10 records from Complex diversity in a mainly tropical group of ant parasitoids: Revision of the Orasema stramineipes species group (Hymenoptera: Chalcidoidea: Eucharitidae). 961 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 104 records from New Zealand Fungal and Plant Disease Collection (PDD). 82316 records from Herbario Amazónico Colombiano. 263 records from Coleópteros de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 52 records from Galathea II, Danish Deep Sea Expedition 1950-52. 197 records from Macroalgas, equinodermos y crustáceos de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 1618 records from Ganadería Colombiana Sostenible (escarabajos coprófagos 2017). 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 100 records from Diversidad de equinodermos en los cayos del norte, Reserva de Biósfera SeaFlower, 2011. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 3 records from NCSM Non-molluscan Invertebrates Collection. 439 records from The AAU Herbarium Database. 192 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 7 records from DSMZ Collection of Plant Viruses. 7 records from Herpetile collection, Natural History Museum, University of Oslo. 2 records from Denver Museum of Nature & Science - Arachnology. 57 records from DMNS Marine Invertebrate Collection (Arctos). 215 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 25 records from New species and new distributional records of Neotropical Mantispidae (Insecta: Neuroptera). 2 records from SJRP-Algae - Herbário de algas de São José do Rio Preto. 5 records from CHAS Malacology Collection (Arctos). 2 records from Elaboración de la base de datos de la colección de cepas de bacterias fitopatógenas de la Dirección General de Sanidad Vegetal. 24 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 836 records from Canadian Museum of Nature Insect Collection. 21 records from MSB Bird Collection (Arctos). 3 records from Naturhistorisches Museum Mainz, Zoological Collection. 2869 records from Flora de los Parques Ecológicos Distritales Humedales de Bogotá D.C.. 7438 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 226 records from Ichthyology Collection - Royal Ontario Museum. 6 records from CHAS Entomology Collection (Arctos). 1 records from UWIZM Phasmatodea. 455 records from Línea base del medio biótico en los bosques para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguablanca -El Morro Yopal. 486 records from Tejidos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 7 records from Two new species of Atopophlebia Flowers, 1980 (Ephemeroptera, Leptophlebiidae) from Colombia. 1241 records from Illinois Natural History Survey Insect Collection. 631 records from CM Herps Collection. 313 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 34 records from Herbaria of the University and ETH Zürich. 5429 records from Aves de tres Macro Hábitats en la región de la Mojana, Sucre, Colombia. 5 records from Phylogenetic analysis of the Neotropical Pristimantis leptolophus species group (Anura: Craugastoridae): molecular approach and description of a new polymorphic species. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 10 records from Scratching the surface? Taxonomic revision of the subgenus Schizoptera (Odontorhagus) reveals vast undocumented biodiversity in the largest litter bug genus Schizoptera Fieber (Hemiptera: Dipsocoromorpha). 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 1925 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 29 records from Caracterización Ecológica de los Mamíferos del Cerro Jánano. 1390 records from MAL. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 71 records from Colección de Referencia de Peces del Museo de Ciencias de la Universidad El Bosque. 2 records from Strongly carinate species of Alpheopsis Coutière, 1897 of the tropical Atlantic and eastern Pacific, with redescription of A. trigona (Rathbun, 1901) and description of three new species (Malacostraca: Decapoda: Alpheidae). 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 30 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 350 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 11 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 27 records from Tejidos de la expedición en el santuario de fauna y flora de Iguaque, Boyacá - Proyecto Boyacá BIO. 399 records from Macrofauna edáfica de ecosistemas asociados a la cuenca hidrográfica del río Orotoy, Meta. 9 records from Collection Crustacea - ZMB. 2 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 39 records from Biologiezentrum Linz. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 1 records from Herbario CTES Plantas Vasculares. 433 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 110 records from Insectos del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 603 records from Registros preliminares del "Catálogo de cangrejos ermitaños del mar Caribe colombiano". 8 records from UConn Mammals. 15 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 14 records from MVZ Egg and Nest Collection (Arctos). 61 records from Planktic foraminifera counts of sediment core RC13-158. 3 records from Collection Onychophora - SMF. 158 records from Planktic foraminifera abundance of Hole 15-151. 12 records from Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil. 265 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 7 records from Edaphobase. 17 records from LSUMZ Bird Tissues. 252 records from Registros de mamíferos recopilados por ProCAT en diferentes zonas de Colombia. 15 records from Inventario de Herpetología Buenos Aires, Tauramena, Casanare. 11 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 34 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 2000 records from Herbario Virtual Bosques Secos de Colombia - Sección Herbario Universidad de Córdoba (HUC). 5 records from Mollusca specimens of Okinawa Prefectural Museum & Art Museum. 140 records from The Fish Collection at the Zoologische Staatssammlung München. 88 records from MPM Herpetology. 5 records from Frost Entomological Museum. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 182 records from Culícidos y élmidos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 714 records from Mosses (S). 111 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 503 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 1 records from Desutterella n. gen., a new genus of Luzarinae (Orthoptera: Grylloidea: Phalangopsidae) and the first report of the Aracambiae group Souza-Dias & Desutter-Grandcolas, 2014 in the Amazon. 1 records from Description of a new genus of Elaphidiini with two new species (Coleoptera, Cerambycidae, Cerambycinae). 5 records from Contributions on Gargaphia (Heteroptera, Tingidae) systematics: redescriptions of two South American species with considerations on the status of G. inca. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 1302 records from Censo de primates de la Fundación Entropika. 63 records from SysTax - Herbaria. 99 records from Australian National Wildlife Collection provider for OZCAM. 9 records from Database of Native Plants in Taiwan. 26 records from Libélulas de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 10822 records from Colección de Insectos de la Universidad del Quindío (CIUQ). 3 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 6 records from Plant bugs (Hemiptera: Miridae) associated with pastures in Colombia. 37 records from CUMV Amphibian and Reptile Collection. 37 records from MPM Milwaukee Public Museum Invertebrate Zoology Collection. 245 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 42 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 232 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 11 records from Fish collection of National Museum of Nature and Science. 1 records from UAM Earth Sciences Collection (Arctos). 4 records from A new species of Leucostethus (Anura: Dendrobatidae) from the eastern versant of the Central Cordillera of Colombia and the phylogenetic status of Colostethus fraterdanieli. 1067 records from Plantas de la cuenca alta y media del río Bita, Vichada (Colombia). 1147 records from Lund Museum of Zoology - Insect collections (MZLU). 64 records from Australian Museum provider for OZCAM. 2 records from An annotated catalogue of the Coleoptera types deposited in the National Insect Collection (CNIN) of the National Autonomous University of Mexico. 4290 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 186 records from Type herbarium, Göttingen (GOET). 1 records from New records of tardigrades from Colombia with the description of Paramacrobiotus sagani sp. nov. and Doryphoribius rosanae sp. nov.. 140 records from Plantas del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 24 records from North Carolina State University Vascular Plant Herbarium. 2 records from A new species of Heterachthes Newman, 1840 from Colombia (Coleoptera, Cerambycidae). 138 records from Cremastosperma (Annonaceae) specimen data. 1 records from Four new species and new synonymy in Stenocerus Schoenherr, 1826 (Coleoptera, Anthribidae, Anthribinae, Stenocerini). 11 records from Taxonomic revision of the Neotropical Myrmicinae ant genus Blepharidatta Wheeler. 1 records from Fossil butterflies, calibration points and the molecular clock (Lepidoptera: Papilionoidea). 4 records from A review of the genus Scaponopselaphus Scheerpeltz (Insecta: Coleoptera: Staphylinidae). 65 records from Taxonomic revision of the Andean harvestman genus Rhaucus Simon, 1879 (Arachnida, Opiliones, Cosmetidae). 5735 records from Colección Zoológica de la Universidad del Tolima (CZUT) - Lepidópteros. 16522 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Chiles-Cumbal, La Cocha-Patascoy y Doña Juana Chimayoy.. 93 records from Coleção de Aves do Museu Nacional / UFRJ. 1942 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Pereira, Risaralda. 2 records from Catalogue of the type specimens of Pogonophora (Annelida; seu Polychaeta: Siboglinidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 1156 records from Colección Entomológica de la Universidad Tecnológica del Chocó. 12 records from Colección de Exhibición de Fósiles del Museo de Ciencias de la Universidad El Bosque. 75 records from Mamiferos de la cuenca alta y media del río Bita, Vichada (Colombia). 39 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 17 records from Museu Paraense Emílio Goeldi - Hexapoda Collection. 43 records from JPB - Herbário Lauro Pires Xavier. 61 records from Canadian Museum of Nature Fish Collection. 694 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 141 records from Caracterizacion de anfibios del Cerro de Chageradó, Frontino- Antioquia). 15 records from Two new species of Huascaromusca Townsend from Colombia, and a new combination for Giovanella carvalhoi (Diptera: Mesembrinellidae). 2 records from ZUEC-COL - Coleção de Coleoptera do Museu de Zoologia da UNICAMP. 3 records from SBMNH Vertebrate Zoology. 62 records from Herbarium (UNA). 511 records from Aves de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 41 records from Fundación Miguel Lillo - Colección Entomológica. 2 records from Revision of the genus Palmanura Cassagnau, 1983 (Collembola: Neanuridae: Neanurinae: Sensillanurini). 152 records from Field Museum of Natural History (Botany) Bryophyte Collection. 1384 records from Aves en el municipio de Medina (Cundinamarca) y San Juanito (Meta) - Proyecto Colombia Bio. 216 records from Mariposas de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 3 records from Occurrence records of southern African aquatic biodiversity. 2 records from Collection Arachnida - SNSD. 37 records from Nineteen new species of Amphidraus Simon, 1900 (Salticidae: Euophryini) from Colombia, with comments about their conservation. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 3 records from Revision of the polytypic electric fish Gymnotus carapo (Gymnotiformes, Teleostei), with descriptions of seven subspecies. 44 records from Inventario de Anfibios y Reptiles Mámbita. 49 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 662 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 4 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 780 records from Comportamiento espacio-temporal de la densidad fitoplanctónica en el año 2015 Magdalena, Colombia. 2041 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 829 records from Colección Ornitológica Universidad de Nariño. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 3022 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 5213 records from Colección de peces de agua dulce del INCIVA. 1 records from Revision of Ogdoecosta Spaeth 1909 with description of Ogdoecosta paraflavomaculata López-Pérez, sp. nov. (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini). 739 records from The Albert J. Cook Arthropod Research Collection. 76 records from Colección de Referencia de Cnidarios del Museo de Ciencias de la Universidad El Bosque. 4982 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 425 records from Plantas de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 972 records from Caracterización de Flora y Fauna en la cuenca del río Calamar, municipios de Bolívar y Trujillo, Valle del Cauca. 818 records from Monitoreo de especies de anfibios en sectores de las reservas forestales Buenavista y Vanguardia en Villavicencio, Meta, como bioindicadores y/o con algún grado de amenaza. 1846 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 66932 records from Bacterias y Arqueas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 8 records from Collection Oligochaeta - ZIM Hamburg. 3 records from Las colecciones del Museu Valencià d'Història Natural. 7 records from Marine invertebrate collection NTNU University Museum. 1419 records from Análisis de integridad biológica en el Parque Natural Regional (PNR) El Vínculo. 1495 records from Insectos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 3 records from LSUMZ Herp Tissues. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 757 records from Evaluación de la biodiversidad del complejo de ciénagas de Caño Negro y Río Cimitarra en la zona de Reserva Campesina del Valle del Río Cimitarra, Colombia, ACVC (Asociación Campesina Valle Río Cimitarra), Laboratorio Dendrología Universidad del Tolima y Universidad de los Andes.. 10 records from An annotated checklist of the Pericopina (Lepidoptera: Erebidae, Arctiinae, Arctiini). 1388 records from Caracterización de aves del borde sur de Bogotá en las localidades de Usme y Ciudad Bolívar. 1101 records from Colección de referencia del Herbario CUVC de la Universidad del Valle. 103 records from UPCB - Herbário do Departamento de Botânica. 2 records from Clarification of the katydid genus Uchuca Giglio-tos, 1898 (Orthoptera: Tettigoniidae): A new species in the Brazilian Amazon Rainforest. 330 records from Fauna asociada (endocárstica) a cuevas en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1331 records from University of Amsterdam (NL) - Páramo pollen reference collection. 315 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 2335 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 39862 records from Field Museum of Natural History (Botany) Seed Plant Collection. 144 records from Herbário da Pontifícia Universidade Católica do Paraná - HUCP. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 1 records from Actualización de la Colección de Collembola de México y ácaros edáficos. Catálogo de oribátidos de México. 1 records from New species and synonymies in Xenopygus Bernhauer (Coleoptera: Staphylinidae: Staphylinini). 3 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 690 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 4 records from Southeastern Louisiana University Herpetology Collection. 6 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 10733 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2127 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 8530 records from Snow Entomological Museum Collection. 823 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidroeléctrica de Calima - 2017. 2661 records from Mammals housed at MHNG, Geneva. 9 records from Arizona State University Charles W. O'Brien Collection. 19 records from Cowan Tetrapod Collection - Birds. 2 records from Swiss Psyllid (Hemiptera) Collections - Basel. 2975 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 37 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 213 records from Natural History Museum Rotterdam (NL) - Insecta collection. 3 records from NPL collections. 1083 records from Diversidad de Mariposas en la Reserva Natural El Romeral. 1 records from MEXU/Agavaceae. 39 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 31 records from Páramo de Belmira as an important centre of endemism in the northern Colombian Andes: new evidence from Pronophilina butterflies (Lepidoptera: Nymphalidae, Satyrinae, Satyrini). 8 records from The species group Amabilis of the genus Euplocania Enderlein (Psocodea: Psocomorpha: Ptiloneuridae). 175 records from Monitoreo biológico en la cuenca Jamundí - Subcuenca Pance Campaña ARA - RARE - CVC – Asociación Calidris. 9 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 12 records from CHAS Mammalogy Collection (Arctos). 8026 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 255 records from Inventario de Plantas Mámbita. 4 records from Collection Anatomie Histologie - SMF. 4 records from Michigan State University Herbarium Vascular Plants. 135 records from Registros biológicos recogidos en el marco del proyecto Census of Marine Life Componente Natural Geography in Shore Areas - NAGISA Santa Marta. 3 records from Description of a new Batrochoglanis species (Siluriformes, Pseudopimelodidae) from the rio Paraguai basin, State of Mato Grosso, Brazil.. 176 records from Jardín Botánico Uniamazonia JBUA. 1090 records from Estudio de Biodiversidad Mina Calenturitas, Temporada de Lluvias. 1475 records from Recopilación de Información de FAUNA en la Jurisdicción de CORNARE, hasta el año 2015. 3388 records from Caracterización biológica en la Serranía de San Lucas 2015. 879 records from Inventario de Fauna vertebrada de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 88 records from DZUP-Hymenoptera - Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 1 records from Zoology (Museum of Evolution - Uppsala). 213 records from Diversity of the Indo-Pacific (DIPnet). 3 records from Rediscovery of Chaetostomus setosus Boulenger 1887 (Siluriformes, Loricariidae), and assessment of the external characters used for determination of genera within the Chaetostoma group. 34 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Platyhelminthes. 2 records from FBIP:ELM: Malacology Collections. 162 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 25 records from Royal BC Museum - Invertebrates Collection. 6 records from Taxonomic revision of the Protopolybia sedula species-group (Hymenoptera, Vespidae, Polistinae), with an new identification key to species. 10 records from Catalog of the types of Coleoptera (Insecta) deposited at Museo de Historia Natural de la Universidad Nacional Mayor de San Marcos (MUSM), Lima, Peru. 168 records from University of Florida Herbarium (FLAS). 1101 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidroeléctrica de Calima. 2017-B.. 102 records from Caracterización poblacional y de hábitat de chigüiros en una ventana de estudio del municipio de Paz de Ariporo, Casanare. 148 records from Reptiles de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 356 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 15 records from Colección Entomológica del IADIZA - CCT CONICET Mendoza: IADIZA-CEI. 624 records from Quirópteros del Parque Natural Regional El Vínculo y su zona de amortiguación (Buga, Valle del Cauca, Colombia). 2 records from Fundación Miguel Lillo - Colección Ornitológica. 4 records from Royal Ontario Museum - Entomology (ROME). 2485 records from Meise Botanic Garden Herbarium (BR). 5298 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 225 records from Biodiversidad de Mamíferos de las Reservas Naturales de la Sociedad Civil del Parque Natural Regional Páramo del Duende, Valle del Cauca, Colombia. 1 records from Perigomphus basicornis sp. nov. (Odonata: Gomphidae) from Anchicayá, Colombia. 253 records from Tejidos de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 11 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 5 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 535 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 41 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 358 records from Caracterización de fauna para el establecimiento de nuevas Reservas Naturales de la Sociedad Civil en Arauca. 68 records from Chinches patinadoras (Hemiptera: Heteroptera: Gerridae) de Colombia: taxonomía, distribución y datos biológicos. 14477 records from Colección de Anfibios del Instituto Alexander von Humboldt. 6 records from Colección de Entomología - Heteroptera. 114 records from Macrohongos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 2 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 27 records from SMNK Mantid Collection. 1 records from The Bergius Herbarium. 6325 records from Colección Entomológica de la Universidad de Antioquia. 205 records from Aves del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 3 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 20 records from Lichen herbarium, Oslo (O). 10 records from Museo Nacional de Ciencias Naturales, Entomología. 14 records from Lichen herbarium, UiB. 87 records from Oregon State Ichthyology Collection. 891 records from Caracterización biológica de la ventana de biodiversidad municipio de Filandia, Quindío, Colombia. 14 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 253 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Albunea paretii. 10 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 629 records from Herpetology Collection NRM. 1 records from Laimosemion leticia (Teleostei: Cyprinodontiformes: Rivulidae), a new species from the upper Rio Amazonas, Southern Colombia. 4 records from FHSM Mammals Collection. 2 records from Coleccion de Herpetologia, MZFC-UNAM. 104 records from Comunidad de Aves presentes en las lagunas del municipio del Medio Baudó. 251 records from Colección Mastozoológica del Museo de Historia Natural de la Universidad del Cauca. 1 records from Taxonomic identity of the ghost ant, Tapinoma melanocephalum (Fabricius, 1793) (Formicidae: Dolichoderinae). 117 records from Fundación Miguel Lillo - Colección Criptogámica. 40 records from UCBG TAPIR Provider. 13 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 93 records from Anfibios de un sector del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO- 2017. 15 records from Crustáceos y moluscos continentales del municipio de Cimitarra, Santander - Proyecto Santander BIO. 1871 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 121 records from Caracterización de fauna terrestre y aves de la cuenca del Río Acacías. 7 records from Fungal Specimens of National Museum of Nature and Science (TNS). 3 records from Entomology at ZMUC, Natural History Musem of Denmark. 3 records from Condon Fossil Collection. 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 1 records from Colección de Entomología - Coleoptera. 67 records from Herbario ABH (Universidad de Alicante). 1 records from Mamíferos marinos de la Reserva de Biósfera Seaflower - Proyecto Colombia BIO. 243 records from Anfibios y reptiles del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 152 records from Investigación y manejo para la conservación de tortugas amenazadas de los humedales llaneros. 31 records from PSM Vertebrates Collection. 4 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 26 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 237239 records from Herbario Nacional Colombiano (COL). 239 records from Biodiversidad de los recursos marinos y costeros entre Cartagena y el Golfo de Urabá, Caribe colombiano. 23 records from PlutoF platform reference-based occurrences. 46 records from Tejidos de Anfibios y Aves, en estudios bióticos en el Complejo de Páramos Chingaza. 28 records from Osaka Prefectural Minoh Park Insects Museum. 8 records from UAZ Herpetology Collection. 255 records from Nannofossil abundance of Hole 15-153. 2 records from INHS wet collections accession. 39774 records from Naturalis Biodiversity Center (NL) - Botany. 4 records from Colección de Zoología Invertebrados - Otros invertebrados. 1 records from Insectarium de Montréal (IMQC). 120 records from CABI Bioscience Genetic Resource Collection. 10786 records from Camera trapping bird data. 1138 records from Primera caracterización biológica de hormigas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 4 records from CSIC-Real Jardín Botánico-Colección de Hongos Histórica (MA-Funhist). 3 records from Description of a new species of Euptychia Hübner, 1818 (Lepidoptera: Nymphalidae: Satyrinae) from the western Andes. 3 records from Naturalis Biodiversity Center (NL) - Museum collection digitized at storage unit level. 6 records from ZUEC-REP - Coleção de Répteis do Museu de Zoologia da UNICAMP. 10 records from ZUEC-AMP - Coleção de Anfíbios do Museu de Zoologia da UNICAMP. 385 records from Biodiversidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 3287 records from Herpetofauna, avifauna y plantas de Puerto Salgar, Caparrapí, Guaduas y Quebradanegra (Cundinamarca). 1 records from Two new ricinuleid species from Ecuador and Colombia belonging to the peckorum species-group of Cryptocellus Westwood (Arachnida, Ricinulei). 4 records from The ant genus Linepithema (Formicidae: Dolichoderinae) in Colombia. 190053 records from Tropicos Specimen Data. 12 records from Caracterización de la Íctiofauna presente en la laguna Concepción, Bocana del río Saija (Cauca), sitio sagrado de las comunidades Indígenas de OZBESCAC. 1506 records from University of Amsterdam (NL) - Páramo vegetation research, Santa Marta and Perijá, Colombia. 4 records from Collection Crustacea - SNSD. 14 records from A cybercatalogue of American sand fly types (Diptera, Psychodidae, Phlebotominae) deposited at the Natural History Museum, London. 14 records from Biological observations from the Dana Expedition Reports. 11729 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Chingaza. 35 records from Revision and phylogenetic analysis of the orb-weaving spider genus Glenognatha Simon, 1887 (Araneae, Tetragnathidae). 1137 records from Plantas Acuáticas de la Orinoquía Colombiana. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 479 records from Biodiversidad microbiana de los ecosistemas marinos en la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 6 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 291 records from Códigos de barras de ADN del marcador COI de aves y tejidos de la colección del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt. 4498 records from Colección Herbario Universidad Católica de Oriente. 97 records from Macroalgas de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 16 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 826 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 955 records from Caracterización biológica de la ventana de biodiversidad Ciénaga, Municipio de Ciénaga, Magdalena, Colombia. 1 records from A preliminary inventory of the catfishes of the lower Rio Nhamundá, Brazil (Ostariophysi, Siluriformes). 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 76 records from Caracterización Floristica del Páramo Tatamá. 71 records from Herbarium Hamburgense. 2348 records from CU Invertebrate Paleontology. 97 records from Diveboard - Scuba diving citizen science observations. 2085 records from Hormigas de la transición matriz - borde - interior de bosque de Fragmentos de Bosque Seco Tropical del Valle del Cauca. 270 records from Monitoreo biológico en la cuenca RUT, campaña ARA - RARE - CVC – Asociación Calidris. 183 records from Instituto de Botánica Darwinion. 24 records from Revision of the genus Callipia Guenée, 1858 (Lepidoptera, Geometridae), with the description of 15 new taxa. 17 records from Zoología Invertebrados - Malacología. 5625 records from AMNH Mammal Collections. 217 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 24 records from Anfibios y reptiles de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 84 records from Colección de Referencia de Equinodermos del Museo de Ciencias de la Universidad El Bosque. 95 records from UAIC Ichthyological Collection. 26 records from Macroinvertebrados de la ciénaga La Honda, Tanguí. 19818 records from ORN. 48 records from Bernice P. Bishop Museum. 606 records from Establecimiento de la Línea Base para el monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidroeléctrica Cucuana. 2017- A. 34 records from BYU Herpetology Collection. 1 records from The species of Psomizopelma Gibson (Hymenoptera: Eupelmidae). 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 3818 records from Inventarios de fauna y flora en los DRMIs Embalse Peñol - Guatapé y Cuenca Alta del Río Guatapé, Las Camelias y el área a declarar Cuenca de San Pedro. 322 records from Macro-invertebrados de la cuenca alta y media del río Bita, Vichada (Colombia). 220 records from DAO Herbarium Type Specimens. 44 records from Colección de Entomología - Orthoptera. 2728 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 2 records from Insect specimens of Iwate Prefectural Museum. 1 records from Systematics and biogeography of Cuban porcelain crabs (Decapoda: Anomura: Porcellanidae). 84 records from Macroinvertebrados de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 151 records from Odonata Collection. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 799 records from Análisis de integridad biológica en el Parque Natural Regional (PNR) Nima. 4 records from Description of two new species of Cryptinglisia Cockerell (Hemiptera: Coccomorpha: Coccidae) associated with rosemary, Rosmarinus officinalis L. (Lamiaceae) in Colombia. 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 16 records from Avistamiento de Aves Corregimientos de Juanchaco y Ladrilleros, Buenaventura, Valle del Cauca - Septiembre 2016. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 1 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 82 records from Actualización de las bases de datos del Herbario XAL. Fase III. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 9 records from UWIZM Scarabaeidae Beetles. 17 records from Taxonomic revision of the New World genus Ariopsis Gill (Siluriformes: Ariidae), with description of two new species. 2 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 1 records from Four new species, taxonomic, and nomenclatural notes in Hammatoderus Gemminger & Harold, 1873 (Coleoptera, Cerambycidae, Lamiinae). 4 records from Small range distributions in the high Andes: two new species of Liaghinella (Hemiptera: Heteroptera: Reduviidae: Emesinae) from Colombia. 21 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 14 records from Naturalis Biodiversity Center (NL) - Tunicata. 18 records from Description of Cathorops mapale, a new species of sea catfish (Siluriformes: Ariidae) from the Colombian Caribbean, based on morphological and mitochondrial evidence.. 23 records from A revision of the genus Bromeloecia Spuler (Diptera: Sphaeroceridae: Limosininae). 80 records from Taxonomic review of Trans-Andean species of Pimelodus (Siluriformes: Pimelodidae), with the descriptions of two new species. 24 records from Apteronotus eschmeyeri, a new species of ghost knifefish from the Magdalena Basin, Colombia (Gymnotiformes: Apteronotidae).. 69 records from Museu Paraense Emilio Goeldi - Lepidoptera Collection. 106 records from Caracterización de la ornitofauna del Alto del Buey, Bahía Solano, Chocó. 543 records from Collection Crustacea SMF. 20 records from Systematic studies on Pseudomyrmex acacia-ants (Hymenoptera: Formicidae: Pseudomyrmecinae). 7 records from Collection Crustacea ZMG. 2012 records from Registros biológicos del género Piper en el herbario HUA. 37 records from Comunidad de Macroinvertebrados de un Área Degradada por Actividad Minera en la Costa Caucana. 81 records from Colección de Referencia de Poliquetos del Museo de Ciencias de la Universidad El Bosque. 118 records from Reptiles de un sector del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia Bio- 2017. 146 records from Tortugas marinas de la Isla Cayos de Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 8 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 2826 records from AntWeb. 256 records from Colección del Herbario del Jardín Botánico de la Universidad Nacional de Colombia Sede Caribe. 29 records from Caracterización de Anfibios del Cerro Tacarcuna, Unguía, Chocó. 10 records from Intermountain Herbarium (Utah State University). 2726 records from Análisis de Integridad Biológica para el Distrito Regional de Manejo Integrado Atuncela. Convenio CVC. Univalle 108 de 2017. 4 records from Uncovering the diversity of the neotropical genus Elaphopsocus (‘ Psocoptera’: Psocidae: Amphigerontiinae): from one to ten species. 7 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 1198 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 13 records from Colección de microorganismos del CINVESTAV-IPN Fase I, Base de datos, Parte Vista Usuarios Internos. 615 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 196 records from Aves de la expedición en el santuario de fauna y flora de Iguaque, Boyacá - Proyecto Boyacá BIO. 5365 records from Bryophyte herbarium, Göttingen (GOET). 294 records from Bee Biology and Systematics Laboratory. 1 records from University of Puerto Rico Mayagüez Invertebrate Collection. 1 records from Revision of Pygoda Amyot & Serville, 1843 stat. rest. (Heteroptera: Pentatomidae: Edessinae) with description of four new species. 22651 records from Colección de sonidos ambientales del Instituto Alexander von Humboldt. 4 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 1 records from MISS_DC_01MAR2006. 3010 records from Coleópteros de la Colección entomológica del Museo de Historia Natural “Luis Gonzalo Andrade” de la UPTC. 716 records from Coleópteros coprófagos y fitófagos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 87 records from Tejidos colectados en la ventana de biodiversidad enclave Atuncela, municipio de Dagua, Valle del Cauca. 1 records from Flora of Japan Specimen Database. 122 records from Peces de agua dulce del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 79 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 4 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 1 records from A new species of Sphelodon Townes (Hymenoptera: Ichneumonidae: Banchinae) from Colombia. 2 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 27 records from Review of the genus Eburodacrys White, 1853 (Coleoptera: Cerambycidae: Cerambycinae). 199 records from Planktic foraminifera abundance of Hole 4-31. 5 records from ISM Ornithology Collection. 3 records from Mammal specimens. 261 records from Tejidos colectados en la ventana de biodiversidad Ciénaga, Municipio de Ciénaga, Magdalena, Colombia. 1 records from MCNH Museum of Cultural and Natural History Mammals Collection. 1098 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 1387 records from Royal Botanic Garden Edinburgh Herbarium (E). 158 records from Biodiversidad del Phyllum Mollusca asociada a las plataformas de explotación de gas natural (Campo Chuchupa: La Guajira, Colombia). 308 records from Caracterización de fauna para la formulación y actualización de Planes de Manejo Ambiental en la jurisdicción de Corpoguavio. 6 records from Characterization of Platymessa with redescription of the type species and a new generic synonymy (Arachnida, Opiliones, Cosmetidae). 117 records from SDNHM Herpetology Collection. 32 records from Speothos Venaticus por Guillermo Gil. 13750 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 210 records from Dicotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 383 records from Lund Botanical Museum (LD). 1695 records from Análisis de Integridad Biológica para el Distrito de Conservación de Suelos Cañón del Río Grande. Convenio CVC- Univalle 108 de 2017. 58 records from FCAB - Herbário Friburguense. 7 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 522 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 34 records from Fiocruz/CLIOC - Coleção de Leishmania. 2 records from Rye, Barley, Oats Genetic Resources. N.I.Vavilov Research Institute of Plant Industry, St. Petersburg. 1198 records from Fauna y flora del municipio de Paipa, Boyacá. 7 records from The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part II: the C. isayae species group, with the description of seven new species. 2 records from SOMBASE. 23 records from Five new species of Buenoa (Hemiptera: Heteroptera: Notonectidae) from Colombia. 181 records from Nymphalidae Ithomiinae. 629 records from RPSP - Coleção Entomológica Prof. J.M.F. Camargo, FFCLRP/USP. 6 records from Registro de Peces presentes en el Centro de acopio del corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de septiembre 2017. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 17 records from Aportes al conocimiento de la biodiversidad de aguas profundas del mar Caribe colombiano. 30 records from Collection Bernstein - SMF. 66 records from Harold W. Manter Laboratory of Parasitology Collection. 163 records from Conectividad migratoria de Protonotaria citrea en la costa Caribe de Colombia. 177494 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 4081 records from Colección Entomológica de la Orinoquia (CEO). 1441 records from Insectos del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 4 records from Zariquiey Collection. Biological Reference Collections ICM CSIC.. 26 records from Paleontological Research Institution Collections. 5 records from Naturalis Biodiversity Center (NL) - Hemiptera. 272 records from Colección Teriológica Universidad de Antioquia. 1 records from A revision of the myrmecophilous genus Smilax Laporte (Coleoptera: Staphylinidae: Staphylininae). 16 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 5 records from The Spider Collection at the Staatliches Museum für Naturkunde Stuttgart. 78 records from MMNH Museum Bird Collection. 7920 records from Lichen Herbarium Berlin. 1015 records from Caracterización vegetal y rasgos funcionales de plantas colectadas en un gradiente altitudinal de bosque altoandino a páramo en el Santuario de Fauna y Flora Iguaque. 629 records from NaGISA Project. 1794 records from Bioversity Collecting Mission Database. 35 records from Crustacea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Museu Paraense Emílio Goeldi - Mastozoology Collection. 3 records from The Vascular Plant Collection at the Herbarium Tubingense. 8386 records from Herbario Museo de La Salle Bogotá (BOG). 5982 records from Caracterización de flora para la formulación y actualización de Planes de Manejo Ambiental en la jurisdicción de Corpoguavio. 205 records from Fortalecimiento de los procesos de recuperación natural y cultural en la Sierra Nevada de Santa Marta. 1844 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 30 records from Colorado Plateau Museum of Arthropod Biodiversity. 6 records from ZFMK Orthopteroidea collection. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 4 records from UFP - Herbário UFP - Geraldo Mariz. 154 records from Tejidos colectados en la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 1777 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 20910 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 1 records from HSU Vertebrate Museum Reptile Collection. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 1 records from Taxonomic revision of the Dasypus kappleri complex, with revalidations of Dasypus pastasae (Thomas, 1901) and Dasypus beniensis Lönnberg, 1942 (Cingulata, Dasypodidae). 2 records from Technomyrmex (Formicidae: Dolichoderinae) in the New World: synopsis and description of a new species.. 1 records from Canadian Museum of Nature Fossil Invertebrate Collection. 5 records from UFG - Herbário da Universidade Federal de Goiás. 59 records from Biodiversidad de Herpetos de las Reservas Naturales de la Sociedad Civil del Parque Natural Regional Páramo del Duende, Valle del Cauca, Colombia. 1684 records from United States National Plant Germplasm System Collection. 1 records from Revision and phylogeny of the genus Balgus Fleutiaux, 1920 (Coleoptera, Elateridae, Thylacosterninae). 1450 records from Colección Zoológica de la Universidad del Tolima (CZUT) - Ornitología. 19 records from Herbarium GAT. 81 records from Aves del Santuario de Fauna y Flora Malpelo entre 2006 y 2013. 37 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 5 records from The genus Waoraniella García Aldrete (Lachesillidae: Eolachesillinae: Waoraniellini) in Colombia: Two new species from the Andean region. 3920 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 25 records from Producción en cautiverio del capitán de la sabana, Eremophilus mutisii, con fines de conservación. 613 records from University of Florida Herpetology. 3 records from Plant specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 7044 records from Field Museum of Natural History (Zoology) Mammal Collection. 13 records from MfN - Fossil invertebrates Ia. 22 records from Ictiofauna Presente en la Ciénaga de Montaño, Municipio del Carmen de Atrato. 2 records from MCNH Museum of Cultural and Natural History Reptile Collection. 15026 records from Monitoreo de aves acuáticas en hábitats sedimentados de la Laguna de Sonso y determinación de la presencia e incidencia de influenza aviar en humedales continentales y costeros del Valle del Cauca.. 3753 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 1 records from University of Texas, Biodiversity Center, Ichthyology Collection (TNHCi). 1341 records from MEL AVH data. 15 records from Canadian Museum of Nature Amphibian and Reptile Collection. 587 records from Caracterización biológica de la ventana de biodiversidad enclave Atuncela, municipio de Dagua, Valle del Cauca. 5112 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 1 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 116 records from Mamíferos del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 3 records from Computarización de la Colección Nacional de Crustáceos del Instituto de Biología, UNAM y elaboración de su catálogo. 31 records from ICN - Herbário do Instituto de Ciências Naturais. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences